Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Imaging and therapy of ovarian cancer: clinical application of nanoparticles and future perspectives. - Di Lorenzo, Giovanni; Ricci, Giuseppe; Severini, Giovanni Maria; Romano, Federico; Biffi, Stefania (Theranostics, 2018)
Despite significant advances in cancer diagnostics and treatment, ovarian cancers (OC) continue to kill more than 150,000 women every year worldwide. Due to the relatively asymptomatic nature and the advanced stage of the disease at the time of diagnosis, OC is the most lethal gynecologic malignancy. The current treatment for advanced OC relies on the synergistic effect of combining surgical cytoreduction and chemotherapy; however, beside the fact that chemotherapy resistance is a major challenge in OC management, new imaging strategies are needed to target microscopic lesions and improve both cytoreductive surgery and patient outcomes. In this context, nanostructured probes are emerging as a new class of medical tool that can simultaneously provide imaging contrast, target tumor cells, and carry a wide range of medicines resulting in better diagnosis and therapeutic precision. Herein we summarize several exemplary efforts in nanomedicine for addressing unmet clinical needs.

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

Impact of near infrared light in pediatric blood drawing Centre on rate of first attempt success and time of procedure. - Conversano, Ester; Cozzi, Giorgio; Pavan, Matteo; Minute, Marta; Gortan, Elena; Montico, Marcella; Vecchi Brumatti, Liza; Ronfani, Luca; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: Peripheral blood access and venipuncture are a stressful and painful experience in pediatric patients; moreover, it is estimated that more than one attempt is required to achieve the procedure in about one third of children. For this reason, we investigated if Near-infrared light technology routinely used, could give an advantage to venipuncture in a pediatric blood center setting. METHODS: We conducted an open, pseudo-randomized controlled trial with two parallel arms, in the blood-drawing center, with enrolment of 115 patients between 0 and 18 years, in 14 consecutive working days. Fifty-three subjects were enrolled in group 1 (VeinViewer®) and 62 in group 2 (control group). We divided patients into three subgroups considering their age (< 5 years, 6-10 years, > 10 years). The primary study outcome was to assess if the use of VeinViewer® was associated with a reduction of time to perform blood sampling. The secondary outcome was to analyze VienViewer®'s impact on first attempt success rate in blood sampling. RESULTS: No difference was found regarding the duration of blood sampling between the two groups, even after stratifying the patients into the three age subgroups. There was no difference between the two groups in the success at the first attempt in blood sampling. CONCLUSIONS: Routine use of VeinViewer® is not useful to reduce time of the procedure during venipuncture. TRIAL REGISTRATION: The study was registered with ClinicalTrials.gov, with number NCT03277092 , on September 8, 2017.
Keywords: Adolescent; Age Factors; Child; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Infrared Rays; Lighting; Male; Phlebotomy; Time Factors

In vivo microbiome and associated immune markers: New insights into the pathogenesis of vaginal dysbiosis. - Campisciano, Giuseppina; Zanotta, Nunzia; Licastro, Danilo; De Seta, Francesco; Comar, Manola (Sci Rep, 2018)
The microbiota fulfils a key role in the training and function of the immune system, which contributes to the symbiosis between the host and complex microbial communities. In this study, we characterized the interplay between vaginal bacteria and local immune mediators during dysbiosis in selected women of reproductive age who were grouped according to Nugent's criteria. The abundance of Gardnerella vaginalis and Bifidobacterium breve was increased in the intermediate dysbiotic status, while the presence of a plethora of non-resident bacteria characterized the group with overt vaginosis. In response to these increases, the anti-inflammatory IL1ra and pro-inflammatory IL2 increased, while the embryo trophic factors FGFβ and GMCSF decreased compared to the healthy milieu. A specific pattern, including IL1α, IL1β, IL8, MIG, MIP1α and RANTES, distinguished the intermediate group from the vaginosis group, while IL5 and IL13, which are secreted by Th2 cells, were significantly associated with the perturbation of the commensals Lactobacilli, Gardnerella and Ureaplasma. Summarizing, we postulate that although the dysbiotic condition triggers a pro-inflammatory process, the presence of a steady state level of Th2 may influence clinical manifestations. These results raise clinically relevant questions regarding the use of vaginal immunological markers as efficacious tools to monitor microbial alterations.
Keywords: Adult; Biomarkers; Cytokines; Dysbiosis; Female; Humans; Microbiota; Th2 Cells; Vagina

Inclusion cyst of anterior fontanelle. - Udina, Chiara; Calligaris, Lorenzo; Berti, Irene; Cattaruzzi, Elisabetta; Barbi, Egidio (Arch Dis Child, 2018)

Infant Analgesia With a Combination of Breast Milk, Glucose, or Maternal Holding. - Bembich, Stefano; Cont, Gabriele; Causin, Enrica; Paviotti, Giulia; Marzari, Patrizia; Demarini, Sergio (Pediatrics, 2018)
OBJECTIVES: We studied neonatal cortical brain response to 4 types of nonpharmacological analgesia (oral glucose, expressed breast milk, maternal holding plus oral glucose, breastfeeding). We aimed to assess the differential effect of oral solutions (glucose, breast milk) given alone or combined with the maternal-infant relationship (holding, breastfeeding). METHODS: Eighty healthy term newborns undergoing a heel stick were randomly assigned to 4 parallel groups of 20 infants each: group 1, infants received a glucose solution on a changing table; group 2, infants received expressed breast milk on a changing table; group 3, infants received a glucose solution in their mothers' arms; and group 4, infants were breastfed by their mothers. Cortical activation in parietal, temporal, and frontal cortices was assessed by multichannel near-infrared spectroscopy. Pain expression was also evaluated. RESULTS: Oral glucose alone or combined with maternal holding was associated with no cortical activation during heel stick. Expressed breast milk was associated with localized bilateral activation of somatosensory and motor cortices ( < .01). Breastfeeding was associated with extensive bilateral activation of somatomotor, somatosensory, and right parietal cortices ( < .01). Pain expression was lower with the maternal-infant relationship ( = .007). CONCLUSIONS: Oral glucose, either alone or combined with maternal holding, appears to block or weaken cortical pain processing. Breast milk alone is associated with localized cortical activation. Breastfeeding is associated with extensive activation and may act by extending cortical processing. Maternal relationship, both combined with oral glucose and in breastfeeding, shows the greatest analgesic effect, although the neural patterns involved are distributed differently.

Influence of polymerization time on properties of dual-curing cements in combination with high translucency monolithic zirconia. - Alovisi, Mario; Scotti, Nicola; Comba, Allegra; Manzon, Elena; Farina, Elena; Pasqualini, Damiano; Michelotto Tempesta, Riccardo; Breschi, Lorenzo; Cadenaro, Milena (J Prosthodont Res, 2018)
PURPOSE: The aim of this in vitro study was to assess conversion degree (DC), micro-hardness (MH) and bond strength of two dual-curing resin cements employed under translucent monolithic zirconia irradiated with different time protocols. METHODS: 84 square shaped samples of 1mm thickness were prepared from high translucency zirconia blocks and divided into two groups (n=24) according to the cement employed: (1) Rely-X Ultimate; (2) Panavia SA. Each group was further divided into 3 subgroups (n=8) according to the irradiation time: (a) no light; (b) 20s; (c) 120s. Light curing was performed 60s after the sample was placed on the diamond support of a FT-IR spectrophotometer with a high power multiLED lamp. Final DC% were calculated after 10min. After 24h, Vickers Test on the cement layer was performed. The same protocol was used to lute composite cylinders in order to evaluate microshear bond-strength test. ANOVA and Bonferroni tests were performed to find differences between MH and bond-strength to zirconia, while for DC% the Scheirer-Ray-Hare two-way test was used. RESULTS: The two cements reached higher DC% in subgroup (b) and (c). As concern MH, statistics showed an increase in curing time was able to improve MH significantly. Bond-strength was not affected by irradiation time only for Panavia SA. CONCLUSIONS: The first null hypothesis has to be rejected since DC% and MH of the dual-cements tested were influenced by the curing time. The second null hypothesis is partially rejected since the bond strength was influenced by the curing time only for Rely-X Ultimate.
Keywords: Composite Resins; Dental Bonding; Dental Cements; Hardness; Lansoprazole; Materials Testing; Polymerization; Resins, Synthetic; Spectrophotometry; Time Factors; Zirconium

Interstitial Fluid in Gynecologic Tumors and Its Possible Application in the Clinical Practice. - Ura, Blendi; Di Lorenzo, Giovanni; Romano, Federico; Monasta, Lorenzo; Mirenda, Giuseppe; Scrimin, Federica; Ricci, Giuseppe (Int J Mol Sci, 2018)
Gynecologic cancers are an important cause of worldwide mortality. The interstitium consists of solid and fluid phases, situated between the blood vessels and cells. The interstitial fluid (IF), or fluid phase, is an extracellular fluid bathing and surrounding the tissue cells. The TIF (tumor interstitial fluid) is a dynamic fluid rich in lipids, proteins and enzyme-derived substances. The molecules found in the IF may be associated with pathological changes in tissues leading to cancer growth and metastatization. Proteomic techniques have allowed an extensive study of the composition of the TIF as a source of biomarkers for gynecologic cancers. In our review, we analyze the composition of the TIF, its formation process, the sampling methods, the consequences of its accumulation and the proteomic analyses performed, that make TIF valuable for monitoring different types of cancers.
Keywords: Biomarkers, Tumor; Biophysical Phenomena; Extracellular Fluid; Female; Genital Neoplasms, Female; Humans; Practice Patterns, Physicians'; Tumor Microenvironment

Intranasal dexmedetomidine, as midazolam-sparing drug, for MRI in preterm neonates. - Bua, Jenny; Massaro, Marta; Cossovel, Francesca; Monasta, Lorenzo; Brovedani, Pierpaolo; Cozzi, Giorgio; Barbi, Egidio; Demarini, Sergio; Travan, Laura (Paediatr Anaesth, 2018)

Investigation of the link between PROP taste perception and vegetables consumption using FAOSTAT data. - Mezzavilla, Massimo; Notarangelo, Michela; Concas, Maria Pina; Catamo, Eulalia; Gasparini, Paolo; Grillotti, Maria Gemma; Robino, Antonietta (Int J Food Sci Nutr, 2018)
In this work we investigated, in populations located in Central Asia, the relationship between PROP taste perception and vegetables liking and consumption using FAOSTAT dataset. Collected data were analysed using distance matrices, Mantel test and Pearson correlation. Populations showing similar ability in tasting PROP bitterness are more similar as respect to vegetable consumption (r = 0.63, p-value = .05). Moreover, a significant negative correlation was found between the percentage of Non Taster (NT) in different countries and the percentage of vegetable consumption (r = -0.87, p-value = .02), while a significant positive correlation emerged between the percentage of Super Taster (ST) and the percentage of vegetable liking (r = 0.87, p-value = .02). In our work we showed that differences in bitter perception among populations contributes to differences in vegetable liking and vegetable consumption. More in detail, populations with higher percentage of ST consume more vegetables than population where the majority of individuals are NT.

Irinotecan-induced muscular contractions. - Naviglio, Samuele; Rabusin, Marco (Pediatr Blood Cancer, 2018)

Iron-related toxicity of single-walled carbon nanotubes and crocidolite fibres in human mesothelial cells investigated by Synchrotron XRF microscopy. - Cammisuli, Francesca; Giordani, Silvia; Gianoncelli, Alessandra; Rizzardi, Clara; Radillo, Lucia; Zweyer, Marina; Da Ros, Tatiana; Salomè, Murielle; Melato, Mauro; Pascolo, Lorella (Sci Rep, 2018)
Carbon nanotubes (CNTs) are promising products in industry and medicine, but there are several human health concerns since their fibrous structure resembles asbestos. The presence of transition metals, mainly iron, in the fibres seems also implicated in the pathogenetic mechanisms. To unravel the role of iron at mesothelial level, we compared the chemical changes induced in MeT-5A cells by the exposure to asbestos (crocidolite) or CNTs at different content of iron impurities (raw-SWCNTs, purified- and highly purified-SWCNTs). We applied synchrotron-based X-Ray Fluorescence (XRF) microscopy and soft X-ray imaging (absorption and phase contrast images) to monitor chemical and morphological changes of the exposed cells. In parallel, we performed a ferritin assay. X-ray microscopy imaging and XRF well localize the crocidolite fibres interacting with cells, as well as the damage-related morphological changes. Differently, CNTs presence could be only partially evinced by low energy XRF through carbon distribution and sometimes iron co-localisation. Compared to controls, the cells treated with raw-SWCNTs and crocidolite fibres showed a severe alteration of iron distribution and content, with concomitant stimulation of ferritin production. Interestingly, highly purified nanotubes did not altered iron metabolism. The data provide new insights for possible CNTs effects at mesothelial/pleural level in humans.
Keywords: Asbestos, Crocidolite; Cell Line; Epithelial Cells; Humans; Iron; Microscopy, Fluorescence; Nanotubes, Carbon

Identification of proteins with different abundance associated with cell migration and proliferation in leiomyoma interstitial fluid by proteomics. - Ura, Blendi; Scrimin, Federica; Franchin, Cinzia; Arrigoni, Giorgio; Licastro, Danilo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Lett, 2017)
Uterine leiomyoma is the most common female reproductive tract benign tumor. Little is known about protein composition and changes in the leiomyoma interstitial fluid (IF). The present study focused on changes in protein abundance in the IF of leiomyoma. Leiomyoma IFs and adjacent myometrial IFs were obtained and analyzed by two-dimensional electrophoresis (2-DE) coupled with mass spectrometry and western blotting for 2-DE data validation. A total of 25 unique proteins were observed to change significantly (P<0.05). Of these proteins with different abundance, 22 had not been previously identified in leiomyoma IF. analysis predicted that three of these proteins were secreted via classical mechanisms, while 22 were secreted via non-classical mechanisms. Ingenuity Pathway Analysis identified 17 proteins associated with cellular migration and proliferation. Among these, phosphoglycerate mutase 1 had not been previously associated with leiomyoma. The abundance of seven proteins was further validated by western blotting. A comparative proteomic approach identified a number of proteins associated with cellular migration and proliferation, with changes in abundance in IF likely to be involved in tumor development. Further studies will be required to investigate the role of these proteins in leiomyoma IF and their possible association with tumor development and growth.

Immediate delivery or expectant management in gestational diabetes at term: the GINEXMAL randomised controlled trial. - Alberico, S; Erenbourg, A; Hod, M; Yogev, Y; Hadar, E; Neri, F; Ronfani, L; Maso, G (BJOG, 2017)
OBJECTIVE: To evaluate maternal and perinatal outcomes after induction of labour versus expectant management in pregnant women with gestational diabetes at term. DESIGN: Multicentre open-label randomised controlled trial. SETTING: Eight teaching hospitals in Italy, Slovenia, and Israel. SAMPLE: Singleton pregnancy, diagnosed with gestational diabetes by the International Association of Diabetes and Pregnancy Study Groups criteria (IADPSGC), between 38 and 39 weeks of gestation, without other maternal or fetal conditions. METHODS: Patients were randomly assigned to induction of labour or expectant management and intensive follow-up. Data were analysed by 'intention to treat'. MAIN OUTCOME MEASURES: The primary outcome was incidence of caesarean section. Secondary outcomes were maternal and perinatal mortality and morbidity. RESULTS: A total of 425 women were randomised to the study groups. The incidence of caesarean section was 12.6% in the induction group versus 11.7% in the expectant group. No difference was found between the two groups (relative risk, RR 1.06; 95% confidence interval, 95% CI 0.64-1.77; P = 0.81). The incidence of non-spontaneous delivery, either by caesarean section or by operative vaginal delivery, was 21.0 and 22.3%, respectively (RR 0.94; 95% CI 0.66-1.36; P = 0.76). Neither maternal nor fetal deaths occurred. The few cases of shoulder dystocia were solved without any significant birth trauma. CONCLUSIONS: In women with gestational diabetes, without other maternal or fetal conditions, no difference was detected in birth outcomes regardless of the approach used (i.e. active versus expectant management). Although the study was underpowered, the magnitude of the between-group difference was very small and without clinical relevance. TWEETABLE ABSTRACT: Immediate delivery or expectant management in gestational diabetes at term?
Keywords: Adult; Delivery, Obstetric; Diabetes, Gestational; Female; Humans; Infant, Newborn; Israel; Italy; Maternal Mortality; Perinatal Mortality; Pregnancy; Pregnancy Outcome; Slovenia; Term Birth; Watchful Waiting

Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Clinical and Hypoxemic Childhood Pneumonia over Three Years in Central Malawi: An Observational Study. - McCollum, Eric D; Nambiar, Bejoy; Deula, Rashid; Zadutsa, Beatiwel; Bondo, Austin; King, Carina; Beard, James; Liyaya, Harry; Mankhambo, Limangeni; Lazzerini, Marzia; Makwenda, Charles; Masache, Gibson; et al. (PLoS One, 2017)
BACKGROUND: The pneumococcal conjugate vaccine's (PCV) impact on childhood pneumonia during programmatic conditions in Africa is poorly understood. Following PCV13 introduction in Malawi in November 2011, we evaluated the case burden and rates of childhood pneumonia. METHODS AND FINDINGS: Between January 1, 2012-June 30, 2014 we conducted active pneumonia surveillance in children <5 years at seven hospitals, 18 health centres, and with 38 community health workers in two districts, central Malawi. Eligible children had clinical pneumonia per Malawi guidelines, defined as fast breathing only, chest indrawing +/- fast breathing, or, ≥1 clinical danger sign. Since pulse oximetry was not in the Malawi guidelines, oxygenation <90% defined hypoxemic pneumonia, a distinct category from clinical pneumonia. We quantified the pneumonia case burden and rates in two ways. We compared the period immediately following vaccine introduction (early) to the period with >75% three-dose PCV13 coverage (post). We also used multivariable time-series regression, adjusting for autocorrelation and exploring seasonal variation and alternative model specifications in sensitivity analyses. The early versus post analysis showed an increase in cases and rates of total, fast breathing, and indrawing pneumonia and a decrease in danger sign and hypoxemic pneumonia, and pneumonia mortality. At 76% three-dose PCV13 coverage, versus 0%, the time-series model showed a non-significant increase in total cases (+47%, 95% CI: -13%, +149%, p = 0.154); fast breathing cases increased 135% (+39%, +297%, p = 0.001), however, hypoxemia fell 47% (-5%, -70%, p = 0.031) and hospital deaths decreased 36% (-1%, -58%, p = 0.047) in children <5 years. We observed a shift towards disease without danger signs, as the proportion of cases with danger signs decreased by 65% (-46%, -77%, p<0.0001). These results were generally robust to plausible alternative model specifications. CONCLUSIONS: Thirty months after PCV13 introduction in Malawi, the health system burden and rates of the severest forms of childhood pneumonia, including hypoxemia and death, have markedly decreased.
Keywords: Child; Child Mortality; Cost of Illness; Dose-Response Relationship, Immunologic; Geography; Humans; Hypoxia; Malawi; Pneumococcal Vaccines; Pneumonia, Pneumococcal; Time Factors; Vaccines, Conjugate

Impaired fasting glucose and impaired glucose tolerance in children and adolescents with overweight/obesity. - Di Bonito, P; Pacifico, L; Chiesa, C; Valerio, G; Miraglia Del Giudice, E; Maffeis, C; Morandi, A; Invitti, C; Licenziati, M R; Loche, S; Tornese, G; Franco, F; et al. (J Endocrinol Invest, 2017)
OBJECTIVE: To investigate in a large sample of overweight/obese (OW/OB) children and adolescents the prevalence of prediabetic phenotypes such as impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), and to assess their association with cardiometabolic risk (CMR) factors including hepatic steatosis (HS). METHODS: Population data were obtained from the CARdiometabolic risk factors in children and adolescents in ITALY study. Between 2003 and 2013, 3088 youths (972 children and 2116 adolescents) received oral glucose tolerance test (OGTT) and were included in the study. In 798 individuals, abdominal ultrasound for identification of HS was available. RESULTS: The prevalence of IFG (3.2 vs. 3.3%) and IGT (4.6 vs. 5.0%) was similar between children and adolescents. Children with isolated IGT had a 2-11 fold increased risk of high LDL-C, non-HDL-C, Tg/HDL-C ratio, and low insulin sensitivity, when compared to those with normal glucose tolerance (NGT). No significant association of IFG with any CMR factor was found in children. Among adolescents, IGT subjects, and to a lesser extent those with IFG, showed a worse CMR profile compared to NGT subgroup. In the overall sample, IGT phenotype showed a twofold increased risk of HS compared to NGT subgroup. CONCLUSIONS: Our study shows an unexpected similar prevalence of IFG and IGT between children and adolescents with overweight/obesity. The IGT phenotype was associated with a worse CMR profile in both children and adolescents. Phenotyping prediabetes conditions by OGTT should be done as part of prediction and prevention of cardiometabolic diseases in OW/OB youth since early childhood.
Keywords: Adolescent; Blood Glucose; Case-Control Studies; Child; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin; Insulin Resistance; Italy; Male; Obesity; Overweight; Prediabetic State; Prevalence

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Improving the quality of hospital care for children by supportive supervision: a cluster randomized trial, Kyrgyzstan. - Lazzerini, Marzia; Shukurova, Venera; Davletbaeva, Marina; Monolbaev, Kubanychbek; Kulichenko, Tatiana; Akoev, Yuri; Bakradze, Maya; Margieva, Tea; Mityushino, Ilya; Namazova-Baranova, Leyla; Boronbayeva, Elnura; Kuttumuratova, Aigul; et al. (Bull World Health Organ, 2017)
OBJECTIVE: To determine whether periodic supportive supervision after a training course improved the quality of paediatric hospital care in Kyrgyzstan, where inappropriate care was common but in-hospital postnatal mortality was low. METHODS: In a cluster, randomized, parallel-group trial, 10 public hospitals were allocated to a 4-day World Health Organization (WHO) course on hospital care for children followed by periodic supportive supervision by paediatricians for 1 year, while 10 hospitals had no intervention. We assessed prospectively 10 key indicators of inappropriate paediatric case management, as indicated by WHO guidelines. The primary indicator was the combination of the three indicators: unnecessary hospitalization, increased iatrogenic risk and unnecessary painful procedures. An independent team evaluated the overall quality of care. FINDINGS: We prospectively reviewed the medical records of 4626 hospitalized children aged 2 to 60 months. In the intervention hospitals, the mean proportion of the primary indicator decreased from 46.9% (95% confidence interval, CI: 24.2 to 68.9) at baseline to 6.8% (95% CI: 1.1 to 12.1) at 1 year, but was unchanged in the control group (45.5%, 95% CI: 25.2 to 67.9, to 64.7%, 95% CI: 43.3 to 86.1). At 1 year, the risk ratio for the primary indicator in the intervention versus the control group was 0.09 (95% CI: 0.06 to 0.13). The proportions of the other nine indicators also decreased in the intervention group ( < 0.0001 for all). Overall quality of care improved significantly in intervention hospitals. CONCLUSION: Periodic supportive supervision for 1 year after a training course improved both adherence to WHO guidelines on hospital care for children and the overall quality of paediatric care.
Keywords: Child; Child Care; Cluster Analysis; Hospitalization; Hospitals, Public; Humans; Kyrgyzstan; Medical Audit; Pediatricians; Professional Role; Prospective Studies; Quality Improvement

Influence of vaginal lactoferrin administration on amniotic fluid cytokines and its role against inflammatory complications of pregnancy. - Maritati, Martina; Comar, Manola; Zanotta, Nunzia; Seraceni, Silva; Trentini, Alessandro; Corazza, Fabrizio; Vesce, Fortunato; Contini, Carlo (J Inflamm (Lond), 2017)
BACKGROUND: An altered amniotic cytokine profile has been reported in inflammatory pregnancy complications with a leading role for IL-6, a marker of the foetal systemic inflammatory response. Up to this date there is no exhaustive information neither on the foetal cytokine balance nor on the best method for its modulation. We aimed to evaluate the influence of vaginal lactoferrin administration on amniotic fluid concentration of 47 cytokines, chemokines and growth factors. METHODS: Sixty women undergoing genetic amniocentesis were enrolled in an open-label clinical trial. 300 mg of vaginal lactoferrin (Florence, Italy) were randomly administered to obtain 3 groups: A, 20 untreated patients; B and C (20 patients in each) respectively treated 4 and 12 h before amniocentesis. Cytokines, chemokines and growth factors concentrations were quantified by a magnetic bead Luminex multiplex immunoassays panel technology. Data analysis was performed with the software Stata (v. 13.1) and GraphPad Prism (v. 5). Group comparisons were performed using Kruskal-Wallis followed by Mann-Whitney U tests, with Bonferroni correction for multiple comparisons. A  < 0.05 was considered significant. RESULTS: Among the 47 tested mediators, 24 (51.06%) were influenced by lactoferrin. 11 (23.4%), showed a highly significant difference (p <0.001); among these IL-9, IL-15, IFN-γ, IP-10, TNF-α, IL-1α and MCP-3 underwent a down-regulation, while IL-17 and FGF-basic, G-CSF, GM-CSF an up-regulation. Difference between group C and both B and A was small for IL-15, IP-10, IL-1α, MCP-3, while it was negligible for IL-9, IFN-γ and TNF-α. IL-17 and the 3 growth factors were strongly enhanced in B and C groups. IL-17, FGF-basic and GM-CSF showed increasing concentrations in both B and C groups, while G-CSF resulted up-regulated only in group C. Significance was intermediate ( < 0.01) for the down regulated IL-2RA, IL-12p40 and IFNα2 (6.38%) while it was small for 10 mediators (21.27%) 7 of which (IL-2, IL-4, eotaxin, PDGF-BB, RANTES, IL-18 and MIF) down-regulated and 3 (MCP-1, IL-3, and SDF-1α) up-regulated. CONCLUSION: Lactoferrin down-regulates 17 pro-inflammatory amniotic mediators while up-regulating 7 anti-inflammatory amniotic mediators, 5 of which definitively belonging to an anti-inflammatory profile. These findings open to clinical investigation on its use against inflammatory complications of pregnancy.

Intra-articular corticosteroids versus intra-articular corticosteroids plus methotrexate in oligoarticular juvenile idiopathic arthritis: a multicentre, prospective, randomised, open-label trial. - Ravelli, Angelo; Davì, Sergio; Bracciolini, Giulia; Pistorio, Angela; Consolaro, Alessandro; van Dijkhuizen, Evert Hendrik Pieter; Lattanzi, Bianca; Filocamo, Giovanni; Verazza, Sara; Gerloni, Valeria; Gattinara, Maurizio; Pontikaki, Irene; et al. (Lancet, 2017)
BACKGROUND: Little evidence-based information is available to guide the treatment of oligoarticular juvenile idiopathic arthritis. We aimed to investigate whether oral methotrexate increases the efficacy of intra-articular corticosteroid therapy. METHODS: We did this prospective, open-label, randomised trial at ten hospitals in Italy. Using a concealed computer-generated list, children younger than 18 years with oligoarticular-onset disease were randomly assigned (1:1) to intra-articular corticosteroids alone or in combination with oral methotrexate (15 mg/m; maximum 20 mg). Corticosteroids used were triamcinolone hexacetonide (shoulder, elbow, wrist, knee, and tibiotalar joints) or methylprednisolone acetate (ie, subtalar and tarsal joints). We did not mask patients or investigators to treatment assignments. Our primary outcome was the proportion of patients in the intention-to-treat population who had remission of arthritis in all injected joints at 12 months. This trial is registered with European Union Clinical Trials Register, EudraCT number 2008-006741-70. FINDINGS: Between July 7, 2009, and March 31, 2013, we screened 226 participants and randomly assigned 102 to intra-articular corticosteroids alone and 105 to intra-articular corticosteroids plus methotrexate. 33 (32%) patients assigned to intra-articular corticosteroids alone and 39 (37%) assigned to intra-articular corticosteroids and methotrexate therapy had remission of arthritis in all injected joints (p=0·48). Adverse events were recorded for 20 (17%) patients who received methotrexate, which led to permanent treatment discontinuation in two patients (one due to increased liver transaminases and one due to gastrointestinal discomfort). No patient had a serious adverse event. INTERPRETATION: Concomitant administration of methotrexate did not augment the effectiveness of intra-articular corticosteroid therapy. Future studies are needed to define the optimal therapeutic strategies for oligoarticular juvenile idiopathic arthritis. FUNDING: Italian Agency of Drug Evaluation.
Keywords: Adrenal Cortex Hormones; Arthritis, Juvenile; Humans; Injections, Intra-Articular; Italy; Methotrexate; Prospective Studies; Treatment Outcome

Intranasal Dexmedetomidine for Procedural Sedation in Children, a Suitable Alternative to Chloral Hydrate. - Cozzi, Giorgio; Norbedo, Stefania; Barbi, Egidio (Paediatr Drugs, 2017)
Sedation is often required for children undergoing diagnostic procedures. Chloral hydrate has been one of the sedative drugs most used in children over the last 3 decades, with supporting evidence for its efficacy and safety. Recently, chloral hydrate was banned in Italy and France, in consideration of evidence of its carcinogenicity and genotoxicity. Dexmedetomidine is a sedative with unique properties that has been increasingly used for procedural sedation in children. Several studies demonstrated its efficacy and safety for sedation in non-painful diagnostic procedures. Dexmedetomidine's impact on respiratory drive and airway patency and tone is much less when compared to the majority of other sedative agents. Administration via the intranasal route allows satisfactory procedural success rates. Studies that specifically compared intranasal dexmedetomidine and chloral hydrate for children undergoing non-painful procedures showed that dexmedetomidine was as effective as and safer than chloral hydrate. For these reasons, we suggest that intranasal dexmedetomidine could be a suitable alternative to chloral hydrate.
Keywords: Administration, Intranasal; Child; Chloral Hydrate; Dexmedetomidine; Humans; Hypnotics and Sedatives

Intranasal Dexmedetomidine Sedation as Adjuvant Therapy in Acute Asthma Exacerbation With Marked Anxiety and Agitation. - Cozzi, Giorgio; Lega, Sara; Giorgi, Rita; Barbi, Egidio (Ann Emerg Med, 2017)
We describe 2 patients with acute asthma exacerbation who were admitted to the emergency department (ED) with severe agitation and restlessness as a prominent finding, for which bedside asthma treatment sedation with intranasal dexmedetomidine was performed. In both cases, dexmedetomidine allowed the patients to rest and improved tolerance to treatment. Dexmedetomidine is a unique sedative with an excellent safety profile and minimal effect on respiratory function. These properties render it particularly promising for the management of severe agitation in children admitted to the ED with acute asthma exacerbation.
Keywords: Acute Disease; Administration, Intranasal; Anxiety; Asthma; Child, Preschool; Dexmedetomidine; Emergency Service, Hospital; Female; Humans; Hypnotics and Sedatives; Infant; Psychomotor Agitation

Introduction of Complementary Foods in a Cohort of Infants in Northeast Italy: Do Parents Comply with WHO Recommendations? - Carletti, Claudia; Pani, Paola; Monasta, Lorenzo; Knowles, Alessandra; Cattaneo, Adriano (Nutrients, 2017)
Timing and type of complementary food in infancy affect nutritional status and health later in life. The objective of this paper was to assess complementary feeding practices, looking at timing, type, and compliance with World Health Organization (WHO) recommendations. Data were obtained from a birth cohort of 400 infants, enrolled in Trieste (Italy) between July 2007 and July 2008 and followed up for three years, using a "food introduction timing table". Five WHO recommendations standards were used to assess parental compliance and associated factors. Thirty seven percent of mothers returned the completed "timing table" up until the child was three years of age. Eighty six percent of infants were already receiving complementary foods at six months. The first food type to be introduced was fresh fruit (170 days from birth, median). Overall, infants shared a very similar diet, which was different from the family diet and characterized by delayed introduction of certain food types. Five percent of parents complied with either all five or only one of the WHO recommendations, 34% with three, and 35% with four. The parents' partial compliance with WHO recommendations is probably due to conflicting information received from different sources. This advocates for national evidence-based guidelines, supported and promoted by health professionals.
Keywords: Adult; Cohort Studies; Dairy Products; Diet; Edible Grain; Female; Follow-Up Studies; Fruit; Humans; Infant; Infant Nutritional Physiological Phenomena; Italy; Logistic Models; Male; Mothers; Patient Compliance; Recommended Dietary Allowances; Socioeconomic Factors; Vegetables; World Health Organization

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

The Italian Society for Pediatric Nephrology (SINePe) consensus document on the management of nephrotic syndrome in children: Part I - Diagnosis and treatment of the first episode and the first relapse. - Pasini, Andrea; Benetti, Elisa; Conti, Giovanni; Ghio, Luciana; Lepore, Marta; Massella, Laura; Molino, Daniela; Peruzzi, Licia; Emma, Francesco; Fede, Carmelo; Trivelli, Antonella; Maringhini, Silvio; et al. (Ital J Pediatr, 2017)
This consensus document is aimed at providing an updated, multidisciplinary overview on the diagnosis and treatment of pediatric nephrotic syndrome (NS) at first presentation. It is the first consensus document of its kind to be produced by all the pediatric nephrology centres in Italy, in line with what is already present in other countries such as France, Germany and the USA. It is based on the current knowledge surrounding the symptomatic and steroid treatment of NS, with a view to providing the basis for a separate consensus document on the treatment of relapses. NS is one of the most common pediatric glomerular diseases, with an incidence of around 2-7 cases per 100000 children per year. Corticosteroids are the mainstay of treatment, but the optimal therapeutic regimen for managing childhood idiopathic NS is still under debate. In Italy, shared treatment guidelines were lacking and, consequently, the choice of steroid regimen was based on the clinical expertise of each individual unit. On the basis of the 2015 Cochrane systematic review, KDIGO Guidelines and more recent data from the literature, this working group, with the contribution of all the pediatric nephrology centres in Italy and on the behalf of the Italian Society of Pediatric Nephrology, has produced a shared steroid protocol that will be useful for National Health System hospitals and pediatricians. Investigations at initial presentation and the principal causes of NS to be screened are suggested. In the early phase of the disease, symptomatic treatment is also important as many severe complications can occur which are either directly related to the pathophysiology of the underlying NS or to the steroid treatment itself. To date, very few studies have been published on the prophylaxis and treatment of these early complications, while recommendations are either lacking or conflicting. This consensus provides indications for the prevention, early recognition and treatment of these complications (management of edema and hypovolemia, therapy and prophylaxis of infections and thromboembolic events). Finally, recommendations about the clinical definition of steroid resistance and its initial diagnostic management, as well as indications for renal biopsy are provided.
Keywords: Adrenal Cortex Hormones; Child; Child, Preschool; Consensus; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Humans; Italy; Male; Nephrotic Syndrome; Practice Guidelines as Topic; Prognosis; Recurrence; Retreatment; Societies, Medical; Survival Rate; Treatment Outcome

The Importance of Mortality Risk Assessment: Validation of the Pediatric Index of Mortality 3 Score. - Wolfler, Andrea; Osello, Raffaella; Gualino, Jenny; Calderini, Edoardo; Vigna, Gianluca; Santuz, Pierantonio; Amigoni, Angela; Savron, Fabio; Caramelli, Fabio; Rossetti, Emanuele; Cecchetti, Corrado; Corbari, Maurizio; et al. (Pediatr Crit Care Med, 2016)
OBJECTIVE: To evaluate the performance of the newest version of the Pediatric Index of Mortality 3 score and compare it with the Pediatric Index of Mortality 2 in a multicenter national cohort of children admitted to PICU. DESIGN: Retrospective, prospective cohort study. SETTING: Seventeen Italian PICUs. PATIENTS: All children 0 to 15 years old admitted in PICU from January 2010 to October 2014. INTERVENTIONS: None. MEASUREMENT AND MAIN RESULTS: Eleven thousand one hundred nine children were enrolled in the study. The mean Pediatric Index of Mortality 2 and 3 values of 4.9 and 3.9, respectively, differed significantly (p < 0.05). Overall mortality rate was 3.9%, and the standardized mortality ratio was 0.80 for Pediatric Index of Mortality 2 and 0.98 for Pediatric Index of Mortality 3 (p < 0.05). The area under the curve of the receiver operating characteristic curves was similar for Pediatric Index of Mortality 2 and Pediatric Index of Mortality 3. The Hosmer-Lemeshow test was not significant for Pediatric Index of Mortality 3 (p = 0.21) but was highly significant for Pediatric Index of Mortality 2 (p < 0.001), which overestimated death mainly in high-risk categories. CONCLUSIONS: Mortality indices require validation in each country where it is used. The new Pediatric Index of Mortality 3 score performed well in an Italian population. Both calibration and discrimination were appropriate, and the score more accurately predicted the mortality risk than Pediatric Index of Mortality 2.

Improving regional universal newborn hearing screening programmes in Italy. - Molini, E; Cristi, M C; Lapenna, R; Calzolaro, L; Muzzi, E; Ciciriello, E; Della Volpe, A; Orzan, E; Ricci, G (Acta Otorhinolaryngol Ital, 2016)
The Universal Newborn Hearing Screening (UNHS) programme aims at achieving early detection of hearing impairment. Subsequent diagnosis and intervention should follow promptly. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for early Identification, Intervention and Care of Hearing Impaired Children", the limitations and strengths of current UNHS programs in Italy have been analysed by a group of professionals working in tertiary centres involved in regional UNHS programmes, using SWOT analysis and a subsequent TOWS matrix. Coverage and lost-to-follow up rates are issues related to UNHS programmes. Recommendations to improve the effectiveness of the UNHS programme have been identified. The need for homogeneous policies, high-quality information and dissemination of knowledge for operators and families of hearing-impaired children emerged from the discussion.

In vitro sensitivity to methyl-prednisolone is associated with clinical response in pediatric idiopathic nephrotic syndrome. - Cuzzoni, E; De Iudicibus, S; Stocco, G; Favretto, D; Pelin, M; Messina, G; Ghio, L; Monti, E; Pasini, A; Montini, G; Decorti, G (Clin Pharmacol Ther, 2016)
The aim of this study was to evaluate the in vitro steroid sensitivity as a predictor of clinical response to glucocorticoids in childhood idiopathic nephrotic syndrome (INS). Seventy-four patients (median age 4.33, interquartile range [IQR] 2.82-7.23; 63.5% male) were enrolled in a prospective multicenter study: in vitro steroid inhibition of patients' peripheral blood mononuclear cell proliferation was evaluated by [methyl-(3) H] thymidine incorporation assay at disease onset (T0) and after 4 weeks (T4) of treatment. Steroid dependence was associated with increased in vitro sensitivity at T4 assessed both as drug concentration inducing 50% of inhibition (IC50 ; odds ratio [OR] = 0.48, 95% confidence interval [CI] = 0.24-0.85; P = 0.0094) and maximum inhibition at the highest drug concentration (Imax ; OR = 1.13, 95% CI = 1.02-1.31; P = 0.017). IC50 > 4.4 nM and Imax < 92% at T4 were good predictors for optimal clinical response. These results suggest that this test may be useful for predicting the response to glucocorticoid therapy in pediatric INS.

Incidence and Estimated Prevalence of Endometriosis and Adenomyosis in Northeast Italy: A Data Linkage Study. - Morassutto, Caterina; Monasta, Lorenzo; Ricci, Giuseppe; Barbone, Fabio; Ronfani, Luca (PLoS One, 2016)
Despite being quite frequent and having serious implications in terms of symptomatology and fertility, data on incidence and prevalence of endometriosis and adenomyosis following gold standard definitions are dramatically lacking. The average time from onset of symptoms to diagnosis in industrialized countries still ranges from five to ten years. Using the regional centralized data linkage system, we calculated incidence and prevalence of endometriosis and adenomyosis in the female population of Friuli Venezia Giulia region, Italy, for the years 2011-2013. Cases were defined as new diagnoses from hospital discharge records, following procedures allowing direct visualization for endometriosis and hysterectomy for adenomyosis, with or without histological confirmation. Diagnoses were considered "new" after verifying women had not been diagnosed in the previous ten years. Incidence of endometriosis and adenomyosis in women aged 15-50 years is 0.14%. Prevalence, estimated from incidence, is 2.00%. Adenomyosis, representing 28% of all diagnoses, becomes increasingly prevalent after the age of 50 years. Our results shows how the study of both endometriosis and adenomyosis should not be limited to women of premenopausal age. Further efforts are needed to sensitize women and health professional, and to find new data linkage possibilities to identify undiagnosed cases.

The incidence rate and prevalence of pediatric type 1 diabetes mellitus (age 0-18) in the Italian region Friuli Venezia Giulia: population-based estimates through the analysis of health administrative databases. - Valent, Francesca; Candido, Riccardo; Faleschini, Elena; Tonutti, Laura; Tortul, Carla; Zanatta, Manuela; Zanette, Giorgio; Zanier, Loris (Acta Diabetol, 2016)
AIMS: The main objective of this study was to estimate the incidence rate and prevalence of pediatric type 1 diabetes mellitus (T1DM; population 0-18 years of age) in the northeastern Italian region Friuli Venezia Giulia and to characterize the subjects affected by the disease. METHODS: This was a retrospective population-based study conducted through the individual-level linkage of several health administrative databases of the Friuli Venezia Giulia region. The incidence rate and prevalence were calculated in the population 0-18 years of age. Using the Mid-p exact method, 95 % confidence intervals for rates were calculated. RESULTS: The incidence rate of pediatric T1DM in the years 2010-2013 was 15.8 new cases/100,000 person-years, peaking in the age class 10-14 years. The rate has increased substantially as compared with the previous regional estimate that dated back to 1993. We observed a seasonal pattern both in the date of birth of the incident cases and in the date of onset of the disease. In the region in 2013, there were 294 prevalent cases (15.1/10,000 inhabitants). Most of them had at least one glycated hemoglobin test in the year. More than 15 % had co-existing autoimmune comorbidities. CONCLUSIONS: The incidence rate of pediatric T1DM in Friuli Venezia Giulia has increased in the last years, and the disease is a relevant public health issue in the region.

Innate and adaptive immunity in self-reported nonceliac gluten sensitivity versus celiac disease. - Di Sabatino, Antonio; Giuffrida, Paolo; Fornasa, Giulia; Salvatore, Chiara; Vanoli, Alessandro; Naviglio, Samuele; De Leo, Luigina; Pasini, Alessandra; De Amici, Mara; Alvisi, Costanza; Not, Tarcisio; Rescigno, Maria; et al. (Dig Liver Dis, 2016)
BACKGROUND: Immune mechanisms have been implicated in nonceliac gluten sensitivity (NCGS), a condition characterized by intestinal and/or extraintestinal symptoms caused by the ingestion of gluten in non-celiac/non-wheat allergic individuals. AIMS: We investigated innate and adaptive immunity in self-reported NCGS versus celiac disease (CD). METHODS: In the supernatants of ex vivo-cultured duodenal biopsies from 14 self-reported NCGS patients, 9 untreated and 10 treated CD patients, and 12 controls we detected innate cytokines - interleukin (IL)-15, tumor necrosis factor-α, IL-1β, IL-6, IL-12p70, IL-23, IL-27, IL-32α, thymic stromal lymphopoietin (TSLP), IFN-α-, adaptive cytokines - interferon (IFN)-γ, IL-17A, IL-4, IL-5, IL-10, IL-13-, chemokines - IL-8, CCL1, CCL2, CCL3, CCL4, CCL5, CXCL1, CXCL10-, granulocyte colony stimulating factor (G-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF). RESULTS: Mucosal innate and adaptive cytokines, chemokines and growth factors did not differ between self-reported NCGS, treated CD and controls. On the contrary, IL-6, IL-15, IL-27, IFN-α, IFN-γ, IL-17A, IL-23, G-CSF, GM-CSF, IL-8, CCL1 and CCL4 were significantly higher in untreated CD than in self-reported NCGS, treated CD and controls, while TSLP was significantly lower in untreated CD than in self-reported NCGS, treated CD and controls. CONCLUSION: In our hands, patients with self-reported NCGS showed no abnormalities of the mucosal immune response.

Iron signature in asbestos-induced malignant pleural mesothelioma: A population-based autopsy study. - Crovella, Sergio; Bianco, Anna Monica; Vuch, Joseph; Zupin, Luisa; Moura, Ronald Rodrigues; Trevisan, Elisa; Schneider, Manuela; Brollo, Alessandro; Nicastro, Enza Maria; Cosenzi, Alessandro; Zabucchi, Giuliano; Borelli, Violetta (J Toxicol Environ Health A, 2016)
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. The development of MPM is frequently linked to inhalation of asbestos fibers. A genetic component of susceptibility to this disease is suggested by the observation that some individuals develop MPM following lower doses of asbestos exposure, whereas others exposed to higher quantities do not seem to be affected. This hypothesis is supported also by frequent reports of MPM familial clustering. Despite the widely recognized role of iron (Fe) in cellular asbestos-induced pulmonary toxicity, the role of the related gene polymorphisms in the etiology of MPM has apparently not been evaluated. Eighty-six single-nucleotide polymorphisms (SNPs) of 10 Fe-metabolism genes were examined by exploiting formalin-fixed paraffin-embedded postmortem samples from 77 patients who died due to MPM (designated AEM) and compared with 48 who were exposed to asbestos but from died in old age of cause other than asbestos (designated AENM). All subjects showed objective signs of asbestos exposure. Three SNPs, localized in the ferritin heavy polypeptide, transferrin, and hephaestin genes, whose frequencies were distributed differently in AEM and AENM populations, were identified. For ferritin and transferrin the C/C and the G/G genotypes, respectively, representing intronic polymorphisms, were significantly associated with protection against MPM and need to be considered as possible genetic markers of protection. Similarly, the C/C hephaestin SNP, a missense variation of this multicopper ferroxidase encoding gene, may be related, also functionally, with protection against MPM. In conclusion, it is proposed that three Fe metabolism-associated genes, significantly associated with protection against development of MPM, may serve as protective markers for this aggressive tumor.
Keywords: Adult; Aged; Asbestos; Autopsy; Case-Control Studies; Female; Ferritins; Gene Frequency; Genetic Markers; Humans; Iron; Lung Neoplasms; Male; Membrane Proteins; Mesothelioma; Middle Aged; Mutation, Missense; Polymorphism, Single Nucleotide; Transferrin; Young Adult

Isolated hypoplasia of abdominal wall muscles associated with fetal ascites. - Travan, Laura; Naviglio, Samuele; Cont, Gabriele; Brovedani, Pierpaolo; Davanzo, Riccardo; Demarini, Sergio (Congenit Anom (Kyoto), 2016)
We report the case of an infant born after parvovirus B19-induced fetal hydrops, who presented at birth with bilateral abdominal wall laxity, which was more evident on the flanks. Imaging exams revealed congenital hypoplasia of oblique abdominal muscles not associated with other anatomical abnormalities except for small liver calcifications. We review the medical literature and identify similar cases associated with fetal ascites. We propose that isolated hypoplasia of abdominal wall muscles can be associated with fetal ascites from various causes, and represents a separate condition from prune belly syndrome.

Isolation of the left innominate artery: a question of connection. - Gesuete, Valentina; Sanabor, Daniela; Benettoni, Alessandra; Bobbo, Marco; Ventura, Alessandro (J Cardiovasc Med (Hagerstown), 2016)

An IBCLC in the Maternity Ward of a Mother and Child Hospital: A Pre- and Post-Intervention Study. - Chiurco, Antonella; Montico, Marcella; Brovedani, Pierpaolo; Monasta, Lorenzo; Davanzo, Riccardo (Int J Environ Res Public Health, 2015)
Published evidence on the impact of the integration of International Board Certified Lactation Consultants (IBCLCs) for breastfeeding promotion is growing, but still relatively limited. Our study aims at evaluating the effects of adding an IBCLC for breastfeeding support in a mother and child hospital environment. We conducted a prospective study in the maternity ward of our maternal and child health Institute, recruiting 402 mothers of healthy term newborns soon after birth. The 18-month intervention of the IBCLC (Phase II) was preceded (Phase I) by data collection on breastfeeding rates and factors related to breastfeeding, both at hospital discharge and two weeks later. Data collection was replicated just before the end of the intervention (Phase III). In Phase III, a significantly higher percentage of mothers: (a) received help to breastfeed, and also received correct information on breastfeeding and community support, (b) started breastfeeding within two hours from delivery, (c) reported a good experience with the hospital staff. Moreover, the frequency of sore and/or cracked nipples was significantly lower in Phase III. However, no difference was found in exclusive breastfeeding rates at hospital discharge or at two weeks after birth.

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Immunologic evidence of a strong association between non-Hodgkin lymphoma and simian virus 40. - Tognon, Mauro; Luppi, Mario; Corallini, Alfredo; Taronna, Angelo; Barozzi, Patrizia; Rotondo, John Charles; Comar, Manola; Casali, Maria Vittoria; Bovenzi, Massimo; D'Agostino, Antonio; Vinante, Fabrizio; Rigo, Antonella; et al. (Cancer, 2015)
BACKGROUND: Non-Hodgkin lymphoma (NHL), the most common cancer of the lymphatic system, is of unknown etiology. The identification of etiologic factors in the onset of NHL is a key event that could facilitate the prevention and cure of this malignancy. Simian virus 40 (SV40) has been considered an oncogenic agent in the onset/progression of NHL. METHODS: In this study, an indirect enzyme-linked immunosorbent assay with 2 synthetic peptides that mimic SV40 antigens of viral capsid proteins 1 to 3 was employed to detect specific antibodies against SV40. Serum samples were taken from 2 distinct cohorts of NHL-affected patients (NHL1 [n = 89] and NHL2 [n = 61]) along with controls represented by oncologic patients affected by breast cancer (BC; n = 78) and undifferentiated nasopharyngeal carcinoma (UNPC; n = 64) and 3 different cohorts of healthy subjects (HSs; HS1 [n = 130], HS2 [n = 83], and HS3 [n = 87]). RESULTS: Immunologic data indicated that in serum samples from NHL patients, antibodies against SV40 mimotopes were detectable with a prevalence of 40% in NHL1 patients and with a prevalence of 43% in NHL2 patients. In HSs of the same median age as NHL patients, the prevalence was 16% for the HS1 group (57 years) and 14% for the HS2 group (65 years). The difference was statistically significant (P < .0001 and P < .001). Interestingly, the difference between NHL1/NHL2 patients and BC patients (40%/43% vs 15%, P < .001) and between NHL1/NHL2 patients and UNPC patients (40%/43% vs 25%, P < .05) was significant. CONCLUSIONS: Our data indicate a strong association between NHL and SV40 and thus a need for innovative therapeutic approaches for this hematologic malignancy.
Keywords: Adult; Aged; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lymphoma, Non-Hodgkin; Male; Middle Aged; Polyomavirus Infections; Seroepidemiologic Studies; Simian virus 40; Tumor Virus Infections

Impact of DEFB1 gene regulatory polymorphisms on hBD-1 salivary concentration. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Ottaviani, Giulia; Gobbo, Margherita; Cecco, Luca; Alberi, Giulia; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2015)
OBJECTIVES: Human β-defensin 1 (hBD-1) is an antimicrobial peptide involved in epithelial defence of various tissues, also present in the saliva. Individual genetic variations within the DEFB1 gene, encoding for hBD-1, could influence gene expression and protein production. DESIGN: Three DEFB1 polymorphisms at 5' untranslated region (UTR), -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362), and two polymorphisms at DEFB1 3' UTR, c*5G > A (rs1047031) and c*87A > G (rs1800971), were analysed by direct sequencing and correlated with hDB-1 salivary concentration (tested with enzyme-linked immunosorbent assay (ELISA)) in 40 healthy subjects. RESULTS: Significant associations were found between individuals presenting different DEFB1 polymorphisms at positions -52 and -44 of the gene and hBD-1 salivary concentrations: -52 G/G carriers had higher levels of protein than G/A and A/A; -44C/G subjects showed a higher protein concentration than homozygous wild-type C/C. For the -20G > A, c*5G > A and c*87A > G polymorphisms, no statistically significant differences were found. Combined haplotype analysis confirmed the results obtained considering the single-nucleotide polymorphisms (SNPs) singularly. CONCLUSION: Polymorphisms in the DEFB1 gene influence hBD-1 production and, therefore, could modify the innate immune system responses and, consequently, the oral health.

Impact of Surgery for Neonatal Gastrointestinal Diseases on Weight and Fat Mass. - De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (J Pediatr, 2015)
OBJECTIVE: To compare growth, fat mass (FM), and fat-free mass in surgical infants vs matched controls at similar postconceptional age (PCA). STUDY DESIGN: Anthropometric and body composition measurements by air-displacement plethysmography (PeaPod-Infant Body Composition System; LMI, Concord, California) were performed at the same PCA in 21 infants who received gastrointestinal surgery and in 21 controls matched for gestational age, birth weight, and sex. RESULTS: Despite similar anthropometry at birth, postsurgical infants were shorter (50.4 [4.7] cm vs 53.2 [4.1] cm, P = .001), lighter (3516 [743] g vs 3946 [874] g, P < .001), and had lower FM content (%FM 14.8 [4.7]% vs 20.2 [5.8]%, P < .0001) than their peers at similar PCA (43 [4] weeks). All surgical infants but 1 (20/21) received parenteral nutrition (PN). Mean PN duration was 40 (30) days. Five infants in the control group received PN because of prematurity for 15 (9-30) days. Nine infants in the surgical group and 1 in the control group had PN-associated cholestasis. CONCLUSIONS: Neonates having surgery for gastrointestinal diseases were shorter, had lower weight, and lower FM content than their peers, despite receiving more PN. Body composition evaluation and monitoring may help optimize growth in these newborns.

Impaired immune response to Candida albicans in cells from Fanconi anemia patients. - Parodi, Alessia; Kalli, Francesca; Svahn, Johanna; Stroppiana, Giorgia; De Rocco, Daniela; Terranova, Paola; Dufour, Carlo; Fenoglio, Daniela; Cappelli, Enrico (Cytokine, 2015)
Fanconi anemia (FA) is a genetic disorder characterized by bone marrow failure and cancer predisposition. Several studies show alterations of the immunological status of FA patients including defects in peripheral blood lymphocyte subsets, serum immunoglobulin levels, and inflammatory cytokines. However scanty information is available on the response of FA cells to specific infectious antigens. In this work we examined the response of FA cells to different immunological stimuli and found a defective response of IL-1β, TNF-α and IL-17 to Candida albicans stimulation thus pointing to a potentially impaired response to fungal infections of FA patients.
Keywords: Adolescent; Candida albicans; CD8-Positive T-Lymphocytes; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Cytokines; Fanconi Anemia; Humans; Immunity; Infant; Young Adult

Improved imputation of low-frequency and rare variants using the UK10K haplotype reference panel. - Huang, Jie; Howie, Bryan; McCarthy, Shane; Memari, Yasin; Walter, Klaudia; Min, Josine L; Danecek, Petr; Malerba, Giovanni; Trabetti, Elisabetta; Zheng, Hou-Feng; Gambaro, Giovanni; Richards, J Brent; et al. (Nat Commun, 2015)
Imputing genotypes from reference panels created by whole-genome sequencing (WGS) provides a cost-effective strategy for augmenting the single-nucleotide polymorphism (SNP) content of genome-wide arrays. The UK10K Cohorts project has generated a data set of 3,781 whole genomes sequenced at low depth (average 7x), aiming to exhaustively characterize genetic variation down to 0.1% minor allele frequency in the British population. Here we demonstrate the value of this resource for improving imputation accuracy at rare and low-frequency variants in both a UK and an Italian population. We show that large increases in imputation accuracy can be achieved by re-phasing WGS reference panels after initial genotype calling. We also present a method for combining WGS panels to improve variant coverage and downstream imputation accuracy, which we illustrate by integrating 7,562 WGS haplotypes from the UK10K project with 2,184 haplotypes from the 1000 Genomes Project. Finally, we introduce a novel approximation that maintains speed without sacrificing imputation accuracy for rare variants.

Increased rate of deleterious variants in long runs of homozygosity of an inbred population from Qatar. - Mezzavilla, Massimo; Vozzi, Diego; Badii, Ramin; Alkowari, Moza Khalifa; Abdulhadi, Khalid; Girotto, Giorgia; Gasparini, Paolo (Hum Hered, 2015)
OBJECTIVE: The aim of this study is to evaluate the fraction of putatively deleterious variants within genomic runs of homozygosity (ROH) regions in an inbred and selected cohort of Qatari individuals. METHODS: High-density SNP array analysis was performed in 36 individuals, and for 14 of them whole-exome sequencing (WES) was also carried out. RESULTS: In all individuals, regions characterized by a high (hotspot) or low (coldspot) degree of homozygosity in all the analysed individuals were mapped, and the most frequent hotspot regions were selected. WES data were exploited to identify the single nucleotide variations (SNVs) harboured by genes located within both regions in each individual. Evolutionary conservation-based algorithms were employed to predict the potential deleteriousness of SNVs. The amount of in silico predicted deleterious SNVs was significantly different (p < 0.05) between homozygosity hotspot and coldspot regions. CONCLUSION: Genes located within ROH hotspot regions contain a significant burden of predicted putatively deleterious variants compared to genes located outside these regions, suggesting inbreeding as a possible mechanism allowing an enrichment of putatively deleterious variants at the homozygous state.
Keywords: Cohort Studies; Consanguinity; Homozygote; Humans; Mutation; Polymorphism, Single Nucleotide; Qatar

Insights from Cardiac Mechanics after Three Decades from Successfully Repaired Aortic Coarctation. - Faganello, Giorgio; Fisicaro, Maurizio; Russo, Giulia; Iorio, Anita; Mazzone, Carmine; Grande, Eliana; Humar, Franco; Cherubini, Antonella; Pandullo, Claudio; Barbati, Giulia; Tarantini, Luigi; Benettoni, Alessandra; et al. (Congenit Heart Dis, 2015)
BACKGROUND AND AIMS: Patients who underwent a successful repair of the aortic coarctation show chronic hyperdynamic state and normal left ventricular (LV) geometry; however, there are few data regarding the LV systolic function in the long term. Accordingly, we assessed LV systolic mechanics and factors associated with LV systolic dysfunction (LVSD) in patients with repaired CoA. METHODS: Clinical and echocardiographic data from 19 repaired CoA were analyzed 28 ± 13 years after surgery. Stress-corrected midwall shortening (sc-MS) and mitral annular peak systolic velocity (S') were analyzed as indexes of LV circumferential and longitudinal systolic function, respectively. Echocardiographic data of CoA patients were compared with 19 patients matched for age and hypertension and 38 healthy controls. Sc-MS was considered impaired if <89%, S' if <8.5 cm/s (10th percentiles of healthy controls, respectively). RESULTS: There were no statistical differences between study groups in LV volumes, mass and geometry. LV ejection fraction and Sc-MS were similar in all groups, however, CoA group had a significantly lower peak S' in comparison with matched and healthy controls (7.1 ± 1.3, 10.3 ± 1.9, and 11.1 ± 1.5, respectively; all P < 0.001). Prevalence of longitudinal LVSD defined as low S' was 84% in CoA, 13% in matched, and 5% in healthy control group (all P<0.05). Multivariate logistic regression analysis revealed that low peak S' was independently related to higher E/E' ratio and the presence of CoA. CONCLUSIONS: Patients who underwent a successful repair of CoA commonly show asymptomatic longitudinal LVSD associated with worse LV diastolic function in the long-term follow-up.

Interleukin-18 gene promoter polymorphisms and celiac disease in Italian patients. - Zupin, Luisa; Catamo, Eulalia; Polesello, Vania; Crovella, Sergio; Segat, Ludovica (Mol Biol Rep, 2015)
Celiac disease (CD) is the most common food-sensitive enteropathy in genetically susceptible individuals. The major genetic risk factors known are specific human leukocyte antigen (HLA)-DQ haplotypes, but other genetic factors are supposed to be involved. Interleukin-18 (IL-18) is a pro-inflammatory cytokine that has an important role in the immune defense and it has the potential to influence inflammatory disorders. IL-18 is able to promote Th1 cell development and it is expressed in the mucosa of the small intestine in celiac patients. Given the IL-18 biological role, and since a few studies have previously suggested its involvement in CD, in order to investigate the role of IL18 gene in the susceptibility to CD we have performed a case-control study, analyzing two IL18 gene promoter polymorphisms, previously reported to impair the transcriptional activity of the gene, (-137G > C and -607C > A, rs187238 and rs1946518 respectively). A total of 556 CD Italian patients and 582 controls, further stratified for HLA class II (DQ) CD risk haplotypes were enrolled. The -607A > C A allele and A/A genotype, as well as the combination of this allele with the -137G allele in the AG haplotype, were associated with an increased risk towards CD development, in particular in HLA-DQ2.2 patients. Although the association was very moderate, our results indicate the possible involvement of IL18 gene in the susceptibility to CD, and for this reason we do think it should deserve further investigation.

Interleukin-18, interleukin-12B and interferon-γ gene polymorphisms in Brazilian patients with rheumatoid arthritis: a pilot study. - Angelo, H D; Gomes Silva, I I F; Oliveira, R D R; Louzada-Júnior, P; Donadi, E A; Crovella, S; Maia, M M D; de Souza, P R E; Sandrin-Garcia, P (Tissue Antigens, 2015)
Polymorphisms in interleukin (IL)-18, IL-12 and interferon (IFN)-γ genes are associated with different levels of cytokines expression and have been associated with rheumatoid arthritis (RA). IL-18 +105 A/C, IL-12B +1188 A/C and IFN-γ +874 T/A polymorphisms were analyzed by restriction fragment length polymorphism-polymerase chain reaction (PCR) and amplification refractory mutation system PCR from 90 RA patients and 186 healthy individuals. There were significant differences to IL-18 +105 A/C polymorphism between the RA and control groups (odds ratio = 3.77; P < 0.0001). Individual carriers of the variant allele C had a 3.77-fold increased risk of for RA (P = 0.0032). No association was observed for IL-12B and IFN-γ polymorphisms. Our finds suggest a possible role for IL-18 polymorphism in the RA susceptibility in studied population.

Intranasal adminsitration of oxytocin in postnatal depression: implications for psychodynamic psychotherapy from a randomized double-blind pilot study. - Clarici, Andrea; Pellizzoni, Sandra; Guaschino, Secondo; Alberico, Salvatore; Bembich, Stefano; Giuliani, Rosella; Short, Antonia; Guarino, Giuseppina; Panksepp, Jaak (Front Psychol, 2015)
Oxytocin is a neuropeptide that is active in the central nervous system and is generally considered to be involved in prosocial behaviors and feelings. In light of its documented positive effect on maternal behavior, we designed a study to ascertain whether oxytocin exerts any therapeutic effects on depressive symptoms in women affected by maternal postnatal depression. A group of 16 mothers were recruited in a randomized double-blind study: the women agreed to take part in a brief course of psychoanalytic psychotherapy (12 sessions, once a week) while also being administered, during the 12-weeks period, a daily dose of intranasal oxytocin (or a placebo). The pre-treatment evaluation also included a personality assessment of the major primary-process emotional command systems described by Panksepp () and a semi-quantitative assessment by the therapist of the mother's depressive symptoms and of her personality. No significant effect on depressive symptomatology was found following the administration of oxytocin (as compared to a placebo) during the period of psychotherapy. Nevertheless, a personality trait evaluation of the mothers, conducted in our overall sample group, showed a decrease in the narcissistic trait only within the group who took oxytocin. The depressive (dysphoric) trait was in fact significantly affected by psychotherapy (this effect was only present in the placebo group so it may reflect a positive placebo effect enhancing the favorable influence of psychotherapy on depressive symptoms) but not in the presence of oxytocin. Therefore, the neuropeptide would appear to play some role in the modulation of cerebral functions involved in the self-centered (narcissistic) dimension of the suffering that can occur with postnatal depression. Based on these results, there was support for our hypothesis that what is generally defined as postnatal depression may include disturbances of narcissistic affective balance, and oxytocin supplementation can counteract that type of affective disturbance. The resulting improvements in well-being, reflected in better self-centering in post-partuent mothers, may in turn facilitate better interpersonal acceptance of (and interactions with) the child and thereby, improved recognition of the child's needs.

Intrapartum fetal heart rate monitoring interpretation in labour: a critical appraisal. - Maso, G; Piccoli, M; De Seta, F; Parolin, S; Banco, R; Camacho Mattos, L; Bogatti, P; Alberico, S (Minerva Ginecol, 2015)
Electronic fetal monitoring (EFM) has been introduced in the obstetrics practice as a test to identify the first signs of fetal deterioration, allowing a prompt intervention to reduce neonatal morbidity and mortality. However, results from clinical trials fail to demonstrate a clear benefit with the use of EFM. No decrease in the incidence of cerebral palsy due to intrapartum asphyxia has been achieved and a significant increase in the rate of operative deliveries and in medico-legal litigations has been observed instead. Despite the lack of evidence supporting its safety and effectiveness, this method is routinely used in the clinical practice and periodical updated guidelines to standardize the method of interpretation and proper actions are proposed. However, limitations still exist and the unavoidable consequences are the increasing rate of caesarean delivery, partly due to a defensive attitude in medical choices, and medico-legal litigations for presumed inappropriate evaluation in case of perinatal adverse event. While Obstetrics Societies are trying to "fight" the rise in caesarean section rates, intrapartum EFM tracings are taken in the court proceedings as one of the main evidences in case of adverse event. The aim of this review is to discuss the limitations of guidelines dealing with intrapartum EFM and the pathophysiological basis to assess the suspicious tracings which represent the most observed and critical issue of EFM interpretation.

Immunomodulation mediated by a herbal syrup containing a standardized Echinacea root extract: a pilot study in healthy human subjects on cytokine gene expression. - Dapas, B; Dall'Acqua, S; Bulla, R; Agostinis, C; Perissutti, B; Invernizzi, S; Grassi, G; Voinovich, D (Phytomedicine, 2014)
In this study, the immunomodulatory effect of a triply standardized Echinacea angustifolia root extract (Polinacea(®)) was evaluated in 10 healthy subjects. Ten ml of syrup containing one hundred mg of extract (corresponding to 4.7 mg of Echinacoside and 8.0mg of a high molecular weight-20,000 Da- polysaccharide) were administered as a herbal syrup once a day for one month. The immunomodulatory effect was evaluated before and after herbal syrup administration evaluating the expression levels of the cytokines IL-2, IL-8, IL-6 and TNF-α. Cytokine expression was studied in lympho-monocytes and in plasma samples measuring the mRNA and protein levels, respectively. The results were analysed by ANOVA and non-parametric Friedman rank sum tests; when possible it was adopted a pair-wise comparisons at different post-treatment times, using the paired t-tests with Holm correction. The correlation between the variations of cytokine plasma levels and the respective mRNA was carried out using a linear regression model. In lympho-monocytes our data indicate the up-regulation of the mRNA levels of IL-2 and IL-8 and the down regulation of the mRNA levels of the pro-inflammatory cytokines TNF-α and IL6. The differential regulation was maximal after 14 days of treatment. IL-2 up-regulation and IL-6 down-regulation were also confirmed at the protein level in plasma. Finally, the up-regulation of the mRNA of IL-2/IL-8 and the down-regulation of IL-6 positively correlated with the protein levels detected in the plasma. In conclusion, this pilot study suggests a relevant role for the standardized Echinacea angustifolia root extract in the control of cytokine expression. This first demonstration of the immuno-modulating activity of Echinacea angustifolia root extract in the healthy subject, supports at least in part the common use of such products as health promoting supplement.
Keywords: Adult; Cytokines; Down-Regulation; Echinacea; Female; Glycosides; Healthy Volunteers; Humans; Immunomodulation; Interleukin-2; Interleukin-6; Interleukin-8; Lymphocytes; Male; Middle Aged; Monocytes; Pilot Projects; Plant Extracts; Plant Roots; Tumor Necrosis Factor-alpha

The implications of diagnosis of small for gestational age fetuses using European and South Asian growth charts: an outcome-based comparative study. - Maso, Gianpaolo; Jayawardane, Mathota A M M; Alberico, Salvatore; Piccoli, Monica; Senanayake, Hemantha M (ScientificWorldJournal, 2014)
The antenatal condition of small for gestational age (SGA) is significantly associated with perinatal morbidity and mortality and it is known that there are significant differences in birth weight and fetal size among different populations. The aim of our study was to assess the impact on outcomes of the diagnosis of SGA according to Bangladeshi and European antenatal growth charts in Sri Lankan population. The estimated fetal weight before delivery was retrospectively reviewed according to Bangladeshi and European growth references. Three groups were identified: Group 1-SGA according to Bangladeshi growth chart; Group 2-SGA according to European growth chart but not having SGA according to Bangladeshi growth chart; Group 3-No SGA according to both charts. There was a difference in prevalence of SGA between Bangladeshi and European growth charts: 12.7% and 51.7%, respectively. There were statistically significant higher rates in emergency cesarean section, fetal distress in labour, and intrauterine death (P < 0.001) in Group 1 compared with Group, 2 and 3. No differences of outcomes occurred between Groups 2 and 3. Our study demonstrated that only cases diagnosed as SGA according to population-based growth charts are at risk of adverse outcome. The use of inappropriate prenatal growth charts might lead to misdiagnosis and potential unnecessary interventions.
Keywords: Asian Continental Ancestry Group; Bangladesh; Birth Weight; Europe; European Continental Ancestry Group; Female; Fetal Growth Retardation; Growth Charts; Humans; Infant, Newborn; Infant, Small for Gestational Age; Pregnancy; Prognosis; Sri Lanka

In vitro endothelial cell proliferation assay reveals distinct levels of proangiogenic cytokines characterizing sera of healthy subjects and of patients with heart failure. - Voltan, Rebecca; Zauli, Giorgio; Rizzo, Paola; Fucili, Alessandro; Pannella, Micaela; Marci, Roberto; Tisato, Veronica; Ferrari, Roberto; Secchiero, Paola (Mediators Inflamm, 2014)
Although myocardial angiogenesis is thought to play an important role in heart failure (HF), the involvement of circulating proinflammatory and proangiogenic cytokines in the pathogenesis and/or prognosis of HF has not been deeply investigated. By using a highly standardized proliferation assay with human endothelial cells, we first demonstrated that sera from older (mean age 52 ± 7.6 years; n = 46) healthy donors promoted endothelial cell proliferation to a significantly higher extent compared to sera obtained from younger healthy donors (mean age 29 ± 8.6 years; n = 20). The promotion of endothelial cell proliferation was accompanied by high serum levels of several proangiogenic cytokines. When we assessed endothelial cell proliferation in response to HF patients' sera, we observed that a subset of sera (n = 11) promoted cell proliferation to a significantly lesser extent compared to the majority of sera (n = 18). Also, in this case, the difference between the patient groups in the ability to induce endothelial cell proliferation correlated to significant (P < 0.05) differences in serum proangiogenic cytokine levels. Unexpectedly, HF patients associated to the highest endothelial proliferation index showed the worst prognosis as evaluated in terms of subsequent cardiovascular events in the follow-up, suggesting that high levels of circulating proangiogenic cytokines might be related to a worse prognosis.
Keywords: Adult; Cell Proliferation; Cells, Cultured; Chemokines; Cytokines; Heart Failure; Human Umbilical Vein Endothelial Cells; Humans; Middle Aged; Neovascularization, Pathologic; Prognosis

In vivo detection of polyomaviruses JCV and SV40 in mesenchymal stem cells from human umbilical cords. - Comar, Manola; Delbue, Serena; Zanotta, Nunzia; Valencic, Erica; Piscianz, Elisa; Del Savio, Rossella; Tesser, Alessandra; Tommasini, Alberto; Ferrante, Pasquale (Pediatr Blood Cancer, 2014)
BACKGROUND: Multipotent stromal cells are present in the Wharton's jelly matrix (WJSC) of the umbilical cord and can be used as an allogeneic source of cells to treat immunological disorders. Recently it was demonstrated that adult bone marrow (BM)-derived mesenchimal stromal cells (MSC) are susceptible to infection with viruses showing potential oncogenic properties, such as the polyomavirus JC (JCV). The aim of this study was to investigate the presence of human polyomaviruses (JCV, BK Virus-BKV, SV40, and Merkel cell polyomavirus-MCPyV) in WJSC, and explore the risk of infection. PROCEDURE: MSC samples from 35 umbilical cords were investigated by quantitative Real Time PCRs for the presence of DNA sequences of JCV, BKV, SV40, and MCPyV. RESULTS: JCV DNA was detected in 1/35 (2.8%) of MSC samples, while SV40 DNA was found in 3/35 (8.6%) of the examined samples. None of the samples showed sequences of BKV and MCPyV. CONCLUSIONS: The present study demonstrates the in vivo ability of polyomaviruses to infect WJSC. Since the therapeutic approach with the WJSC has high potentiality and a more intensive use can be easily hypothesized, the need to develop consensus guidelines to detect rare viral infections in MSC is pressing.
Keywords: DNA, Viral; Female; Fetal Blood; Humans; JC Virus; Male; Mesenchymal Stromal Cells; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Increased levels of C-C chemokine RANTES in asbestos exposed workers and in malignant mesothelioma patients from an hyperendemic area. - Comar, Manola; Zanotta, Nunzia; Bonotti, Alessandra; Tognon, Mauro; Negro, Corrado; Cristaudo, Alfonso; Bovenzi, Massimo (PLoS One, 2014)
BACKGROUND: Asbestos-induced mesothelial inflammatory processes are thought to be the basic mechanisms underlying Malignant Mesothelioma (MM) development. Detection of MM often occurs at late stage due to the long and unpredictable latent period and the low incidence in asbestos exposed individuals. The aim of this study was to investigate early immunological biomarkers to characterize the prognostic profile of a possible asbestos-induced disease, in subjects from a MM hyperendemic area. METHODS: The Luminex Multiplex Panel Technology was used for the simultaneous measurement of serum levels of a large panel of 47 analytes, including cytokines and growth factors, from workers previously exposed to asbestos (Asb-workers), asbestos-induced MM patients and healthy subjects. In addition, to explore the influence on serum cytokines profile exerted by SV40 infection, a cofactor in MM development, a quantitative real time PCR was performed for sequences detection in the N-terminal and intronic regions of the SV40 Tag gene. Statistical analysis was done by means of the Mann-Whitney test and the Kruskall-Wallis test for variance analysis. RESULTS: A variety of 25 cytokines linked to pulmonary inflammation and tumor development were found significantly associated with Asb-workers and MM patients compared with healthy controls. A specific pattern of cytokines were found highly expressed in Asb-workers: IFN-alpha (p<0.05), EOTAXIN (p<0.01), RANTES (p<0.001), and in MM patients: IL-12(p40), IL-3, IL-1 alpha, MCP-3, beta-NGF, TNF-beta, RANTES (p<0.001). Notably, the chemokine RANTES measured the highest serum level showing an increased gradient of concentration from healthy subjects to Asb-workers and MM patients (p<0.001), independently of SV40 infection. CONCLUSION: This study shows that, in subjects from an hyperendemic area for MM, the C-C chemokine RANTES is associated with the exposure to asbestos fibres. If validated in larger samples, this factor could have the potential to be a critical biomarker for MM prognosis as recently reported for breast tumor.
Keywords: Aged; Aged, 80 and over; Asbestos; Biomarkers, Tumor; Case-Control Studies; Chemokine CCL5; Cytokines; Endemic Diseases; Gene Expression; Gene Expression Profiling; Humans; Lung Neoplasms; Mesothelioma; Middle Aged; Occupational Exposure; Simian virus 40; Viral Proteins

Influence of HLA-G polymorphisms in human immunodeficiency virus infection and hepatitis C virus co-infection in Brazilian and Italian individuals. - da Silva, G K; Vianna, Priscila; Veit, Tiago Degani; Crovella, Sergio; Catamo, Eulalia; Cordero, Elvira Alicia Aparicio; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Chies, José Artur Bogo (Infect Genet Evol, 2014)
OBJECTIVE: This study aimed to investigate the role of Human Leukocyte Antigen (HLA)-G in the susceptibility to HIV-1 infection through the analysis of the HLA-G 3' untranslated region (UTR) polymorphisms 14 bp insertion/deletion (rs66554220) and +3142C>G (rs1063320). DESIGN: We analyzed 582 HIV-1 infected patients and 626 uninfected individuals from Brazil and Italy in a case-control study. METHODS: HLA-G polymorphisms were genotyped using PCR, PCR-RFLP assays or direct sequencing. All analyses were stratified by ethnicity. Genotypic, allelic and diplotypic frequencies were compared between HIV-1 infected subjects and controls using Chi-square or Fischer exact tests. Also, haplotypic frequencies were estimated using MLocus software. RESULTS: African-derived HIV-infected individuals presented a higher frequency of the 14 bp insertion allele as compared to non-infected individuals (0.468 versus 0.373, respectively; p(Bonf) = 0.010). A higher frequency of the 14 bp insertion +3142G (insG) haplotype (0.456 versus 0.346, p<0.001) and the insG/insG diplotype (OR=1.88, 95%CI = 1.08-3.23, p=0.021) was observed among African-derived patients as compared to uninfected controls. Also, we observed a higher frequency of the ins/ins genotype among African-derived HIV patients co-infected with HCV (OR=2.78, 95%CI = 1.20-6.49, p = 0.008). CONCLUSIONS: Our data point out to an increased frequency of alleles and genotypes associated with low HLA-G expression among African-derived patients, suggesting a potential role for HLA-G in the susceptibility to HIV-1 infection and HCV co-infection in those individuals.
Keywords: 3' Untranslated Regions; Adolescent; Adult; African Continental Ancestry Group; Aged; Brazil; Coinfection; Gene Frequency; Genetic Variation; Haplotypes; Hepatitis C; HIV Infections; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Influence of urine volume on the assessment of intestinal permeability in affected children by multiple sugar probes. - Addobbati, Riccardo; Pascolo, Lorella; Di Toro, Nicola; Sebastiani, Giulia B; Martellossi, Stefano; Not, Tarcisio (Clin Chem Lab Med, 2014)
BACKGROUND: In this study we have looked at the reliability of a multi-sugar test in a pediatric patient population and its accuracy at small urine volumes to evaluate intestinal permeability. METHODS: Out of 117 subjects enrolled, 31 were healthy and 86 were sick. A solution containing lactulose, rhamnose, sucrose, and sucralose was administered to subjects who were on fasting; the urine excreted during 5 h was collected and measured. Samples were analyzed by gas chromatography-tandem mass spectrometry and results were expressed as percentage of sugar recoveries and lactulose/rhamnose (L/R) ratio. RESULTS: The analyses showed a clear effect of low urinary volumes (≤240 mL) particularly affecting rhamnose excretion in healthy subjects and sucrose and sucralose recovery in diseased children. Despite the low rhamnose recovery, as lactulose is not similarly affected, the diagnostic reliability of L/R ratio is well preserved at low diuresis conditions. However, this ratio can be useful to discriminate acute conditions vs. clinical remissions only at high urine volumes. Data also suggest potential diagnostic applicability of sucrose and sucralose in children at high urine volumes. CONCLUSIONS: In conclusion, the multi-sugar test has a good predictivity in pediatric subjects but results must be carefully interpreted in the face of reduced diuresis.
Keywords: Carbohydrates; Child, Preschool; Diuresis; Female; Gas Chromatography-Mass Spectrometry; Gastrointestinal Diseases; Humans; Infant; Intestines; Lactulose; Male; Permeability; Rhamnose; Sucrose

Informed consent, and an ethico-legal framework for paediatric observational research and biobanking: the experience of an Italian birth cohort study. - Toccaceli, Virgilia; Serino, Laura; Stazi, Maria Antonietta (Cell Tissue Bank, 2014)
Birth cohort studies are important tools for life-course epidemiology, given the spectrum of the environmental, behavioural, and genetic factors that should be considered when making judgements on human health. Biobanks are valuable components of studies designed to investigate the genetic variability of diseases and improve phenotypic characterisation. In studies involving vulnerable populations and biobanks, it is essential to provide ethical reasoning and analyse the legal requirements. We describe the processes and the tools used in the iterative design of an appropriate informed consent model and the ethico-legal framework of the Piccolipiù study. The Piccolipiù study is a prospective population-based study funded by the Italian Ministry of Health that intends to enrol 3,000 newborns and their mothers in five Italian cities, and to store biological samples for future use. To realise these objectives, we performed a thorough evaluation of the literature, of national and international guidelines, and of the impact of the Italian legal requirements for research biobanking. Discussions among stakeholders facilitated the design of the informed consent and the ethico-legal framework. Several topics are addressed, including the suitability of a broad informed consent for paediatric biobanks, infant vulnerability, access to and sharing of data, and the disclosure of individual's genetic results. Discussion of the ethical and legal procedures adopted in epidemiological biobanking might be a fruitful ground for comparison both at the national level, where standardization and homogeneity are lacking, and at the international level, where different regulatory issues are often in the background and might hamper research biobanks networking.
Keywords: Cohort Studies; Confidentiality; Databases, Genetic; Genetic Privacy; Genetic Research; Genotype; Humans; Infant, Newborn; Information Dissemination; Informed Consent; Internationality; Italy; Parents; Phenotype

Inhibition of mesenchymal stromal cells by pre-activated lymphocytes and their culture media. - Valencic, Erica; Loganes, Claudia; Cesana, Stefania; Piscianz, Elisa; Gaipa, Giuseppe; Biagi, Ettore; Tommasini, Alberto (Stem Cell Res Ther, 2014)
INTRODUCTION: Despite having a proven immunosuppressive potential in vitro, human mesenchymal stromal cells (MSCs) are reported to display variable efficacy in vivo and, in fact, their proven benefit in the clinical practice is still limited and controversial. METHODS: The interplay between clinical grade MSCs and pre-activated donor lymphocytes or selected lymphocyte subsets was studied in vitro. The kinetics of MSC growth and viability was evaluated by adhesion-dependent changes of culture plate impedance and biochemically by a colorimetric assay. Activation of natural killer (NK) cells was assessed as well, using a flow cytometry assay. RESULTS: A strong inhibition of MSC growth was rapidly induced by the addition of pre-activated lymphocytes but not of resting lymphocytes. Inhibition seems not to be attributable to a single cell population, as similar results can be obtained by depleting NK cells or by using either selected CD4+ or CD8+ lymphocytes. In addition, conditioned medium (CM) from activated lymphocytes was able to inhibit MSC growth in a dose-dependent manner. Furthermore, licensing with IFN-γ partially protected MSCs from pre-activated lymphocytes but not from their CM. These results suggest an inhibitory role of lymphocyte-activation-derived substances. However, the identification of a single molecule responsible for MSC inhibition remained elusive, even if preliminary experiments showed that ATP and, to a lesser extent, TNF-α might play a role. CONCLUSIONS: These results suggest that survival of MSCs can be affected by soluble mediators released by activated lymphocytes. Thus it can be hypothesized that MSC immunosuppressive action in vivo could be impaired by ongoing immune activation through the release of inflammatory mediators.
Keywords: CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Cell Survival; Cells, Cultured; Coculture Techniques; Culture Media, Conditioned; Cytokines; Humans; Killer Cells, Natural; Lymphocyte Activation; Mesenchymal Stromal Cells

Insight into genetic determinants of resting heart rate. - Mezzavilla, Massimo; Iorio, Annamaria; Bobbo, Marco; D'Eustacchio, Angela; Merlo, Marco; Gasparini, Paolo; Ulivi, Sheila; Sinagra, Gianfranco (Gene, 2014)
BACKGROUND: Recent studies suggested that resting heart rate (RHR) might be an independent predictor of cardiovascular mortality and morbidity. Nonetheless, the interrelation between RHR and cardiovascular diseases is not clear. In order to resolve this puzzle, the importance of genetic determinants of RHR has been recently suggested, but it needs to be further investigated. OBJECTIVE: The aim of this study was to estimate the contribution of common genetic variations on RHR using Genome Wide Association Study. METHODS: We performed a Genome Wide Association Study in an isolated population cohort of 1737 individuals, the Italian Network on Genetic Isolates - Friuli Venezia Giulia (INGI-FVG). Moreover, a haplotype analysis was performed. A regression tree analysis was run to highlight the effect of each haplotype combination on the phenotype. RESULTS: A significant level of association (p<5 × 10(-8)) was detected for Single Nucleotide Polymorphisms (SNPs) in two genes expressed in the heart: MAML1 and CANX. Founding that the three different variants of the haplotype, which encompass both genes, yielded a phenotypic correlation. Indeed, a haplotype in homozygosity is significantly associated with the lower quartile of RHR (RHR ≤ 58 bpm). Moreover no significant association was found between cardiovascular risk factors and the different haplotype combinations. CONCLUSION: Mastermind-like 1 and Calnexin were found to be associated with RHR. We demonstrated a relation between a haplotype and the lower quartile of RHR in our populations. Our findings highlight that genetic determinants of RHR may be implicated in determining cardiovascular diseases and could allow a better risk stratification.
Keywords: Calnexin; Cardiovascular Diseases; DNA-Binding Proteins; Female; Genome-Wide Association Study; Haplotypes; Heart Rate; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Transcription Factors

Interleukin-10 gene promoter polymorphisms in celiac patients from north-eastern Italy. - Zupin, Luisa; Polesello, Vania; Catamo, Eulalia; Crovella, Sergio; Segat, Ludovica (Hum Immunol, 2014)
Celiac disease is a complex chronic intestinal disorder driven by an immune response against the gliadin fraction of gluten: many factors are involved in the pathogenesis of the disease, and among these Interleukin-10 could play an important role. In the present study, the -1082A>G, -819T>C and -592A>C IL10 functional polymorphisms were analyzed in 565 celiac patients and 576 healthy controls from north-eastern Italy, stratified for HLA class II celiac disease risk haplotypes. No significant differences were observed for the three IL10 polymorphisms distribution between celiac patients and controls with the exception of a slightly increased risk for the -1082A allele in HLA-DQ8 male individuals. Although our findings suggest that the IL10 genetic variants analyzed do not have a major role in the susceptibility to the development of celiac disease in north-eastern Italian patients, we think that the possible involvement of IL10 gene in CD should deserve further investigation and that large-scale studies are recommended to confirm our findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Celiac Disease; Child; Child, Preschool; European Continental Ancestry Group; Female; Gene Frequency; HLA-DQ Antigens; Humans; Interleukin-10; Italy; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Risk Factors; Sex Factors

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Inverse correlation between circulating levels of TNF-related apoptosis-inducing ligand and 17β-estradiol. - Zauli, Giorgio; Tisato, Veronica; Melloni, Elisabetta; Volpato, Stefano; Cervellati, Carlo; Bonaccorsi, Gloria; Radillo, Oriano; Marci, Roberto; Secchiero, Paola (J Clin Endocrinol Metab, 2014)
CONTEXT: The regulation of the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a cytokine of the TNF family, playing a key role in the immune surveillance against cancer, is incompletely understood. OBJECTIVE: The objective of the study was to investigate the potential link between TRAIL and 17β-estradiol. DESIGN, SETTING, AND PARTICIPANTS: Circulating TRAIL levels were measured by an ELISA in plasma samples (n = 246) of healthy, age-matched (range 30-70 y) men and women and in the sera (n = 180) of females belonging to different physiopathological conditions (childhood, pregnancy, under gonadotropin treatment, menopause) characterized by different levels of circulating 17β-estradiol. RESULTS: TRAIL plasma levels in women with aged younger than 50 years were significantly lower compared with age-matched men, whereas in woman 50 years old or older, TRAIL levels were significantly higher compared with the age-matched men and with the younger women. Moreover, an analysis of women with different conditions revealed a significant inverse correlation between the serum levels of TRAIL and 17β-estradiol, with the lowest levels of TRAIL being observed during pregnancy and the highest in childhood and in postmenopausal women. Moreover, gonadotropin treatment in women undergoing assisted reproduction was accompanied by an acute decrease of serum TRAIL levels. Finally, in vitro treatment with 17β-estradiol decreased the TRAIL expression levels in peripheral blood mononuclear cells. CONCLUSIONS: Our data suggest that 17β-estradiol plays a role in regulating TRAIL circulating levels. The demonstration that postmenopausal women exhibit the highest TRAIL levels is of particular interest in light of a previous large study population showing that TRAIL is positively correlated to the overall survival.
Keywords: Adult; Aged; Case-Control Studies; Child; Child, Preschool; Estradiol; Female; Humans; Infant; Male; Middle Aged; Pregnancy; Sex Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Infantile bilateral glaucoma in a child with ectodermal dysplasia. - Callea, Michele; Vinciguerra, Agatino; Willoughby, Colin E; Deroma, Laura; Clarich, Gabriella (Ophthalmic Genet, 2013)
Ectodermal dysplasia is a rare disease which affects at least two ectodermal-derived structures such as hair, nails, skin, sweat glands and teeth. Approximately 200 different conditions have been classified as an ectodermal dysplasia and X-linked hypohidrotic ectodermal dysplasia (XHED) represents the commonest form. Clinically, XHED is characterized by hypotrichosis, hypohidrosis and hypodontia. A variety of ocular manifestations have been reported in XHED, the most common being dryness of eyes due to tear deficiency and instability of the film secondary to the absence of meibomian gland function. Here we report a child with the distinctive clinical features of XHED confirmed with molecular diagnosis who presented with infantile bilateral glaucoma, in addition to the classical ocular involvement in XHED.
Keywords: Antihypertensive Agents; Child; Ectodermal Dysplasia; Ectodysplasins; Humans; Hydrophthalmos; Intraocular Pressure; Male; Mutation; Polymorphism, Single Nucleotide; Tonometry, Ocular

Identification of a New Mutation (L46P) in the Human NOG Gene in an Italian Patient with Symphalangism Syndrome. - Athanasakis, E; Biarnés, X; Bonati, M T; Gasparini, P; Faletra, F (Mol Syndromol, 2012)
Proximal symphalangism (SYM1) is a joint morphogenesis disorder characterized by stapes ankylosis, proximal interphalangeal joint fusion, skeletal anomalies and conductive hearing loss. Noggin is a bone morphogenetic protein (BMP) antagonist essential for normal bone and joint development in humans and mice. Autosomal dominant mutations have been described in the NOG gene, encoding the noggin protein. We analyzed an Italian sporadic patient with SYM1 due to a novel NOG mutation (L46P) based on a c.137T>C transition. A different pathogenic mutation in the same codon (L46D) has been previously described in an in vivo chicken model. An in silico model shows a decreased binding affinity between noggin and BMP7 for both L46D and L46P compared to the wild type. Therefore, this codon should play an important role in BMP7 binding activity of the noggin protein and consequently to the joint morphogenesis.

Immunomodulatory drugs in autoimmune lymphoproliferative syndrome (ALPS). - Tommasini, Alberto; Valencic, Erica; Piscianz, Elisa; Rabusin, Marco (Pediatr Blood Cancer, 2012)
Keywords: Antineoplastic Agents; Autoimmune Lymphoproliferative Syndrome; Diseases in Twins; Humans; Male; Pentostatin

Importance of bladder bowel dysfunction in patients with urinary tract infection. - Giurici, Nagua; Pennesi, Marco (J Pediatr, 2012)
Keywords: Cystoscopy; Female; Fever; Humans; Male; Ureteroscopy; Urinary Tract Infections; Vesico-Ureteral Reflux

In vivo anti-lymphoma activity of an agonistic human recombinant anti-TRAIL-R2 minibody. - Zauli, Giorgio; Corallini, Federica; Zorzet, Sonia; Grill, Vittorio; Marzari, Roberto; Secchiero, Paola (Invest New Drugs, 2012)
A new single-chain fragment variable (scFv) to TRAIL-R2 receptor produced as minibody (MB2.23) was characterized for anti-lymphoma activity in vivo. For this purpose, a disseminated lymphoma model was generated by intraperitoneal inoculation of BJAB cells in severe combined immunodeficiency mice. Two weekly injections with MB2.23 (10 mg/kg) were able to significantly increase the median survival time of lymphoma-bearing animals with respect to the vehicle-treated control mice, providing a rationale for further investigating the use of MB2.23 in anticancer therapy.
Keywords: Animals; Humans; Immunotherapy; Injections, Intraperitoneal; Lymphoma, B-Cell; Mice; Mice, SCID; Receptors, TNF-Related Apoptosis-Inducing Ligand; Single-Chain Antibodies; Time Factors; Xenograft Model Antitumor Assays

Inflammation profile of four early onset Crohn patients. - Marcuzzi, Annalisa; Girardelli, Martina; Bianco, Anna Monica; Martelossi, Stefano; Magnolato, Andrea; Tommasini, Alberto; Crovella, Sergio (Gene, 2012)
Crohn disease (CD) is a multifactorial disorder affecting mainly young adults. Sometimes, however, it can present in the first year of life (Early onset Crohn disease (EOCD)) showing an unpredictable course and can often be more severe than at older ages. Some cases have been associated to an underlying primary immunodeficiency such as IL10R deficiency. We studied the functional response to IL-10 and the genotype of IL-10 receptor in four patients with early onset crohn-like colitis. We found an IL10R variant, which may be associated with a decreased response to the cytokine in one patient. Further studies to determine its pathogenic effect should be performed. In addition IL-10 mediated inhibition of LPS-induced TNFα expression was measured in patient's monocytes.
Keywords: Crohn Disease; Cytokines; Humans; Inflammation; Monocytes; Nod2 Signaling Adaptor Protein; Polymorphism, Genetic; Receptors, Interleukin-10; Tumor Necrosis Factor-alpha

Influence of age, sex and ethnicity on platelet count in five Italian geographic isolates: mild thrombocytopenia may be physiological. - Biino, Ginevra; Gasparini, Paolo; d'Adamo, Pio; Ciullo, Marina; Nutile, Teresa; Toniolo, Daniela; Sala, Cinzia; Minelli, Cosetta; Gögele, Martin; Balduini, Carlo L (Br J Haematol, 2012)
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Middle Aged; Platelet Count; Reference Values; Sex Distribution; Thrombocytopenia; Young Adult

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

International collaboration as a tool for diagnosis of patients with inherited thrombocytopenia in the setting of a developing country. - Glembotsky, A C; Marta, R F; Pecci, A; De Rocco, D; Gnan, C; Espasandin, Y R; Goette, N P; Negro, F; Noris, P; Savoia, A; Balduini, C L; Molinas, F C; et al. (J Thromb Haemost, 2012)
BACKGROUND: Inherited thrombocytopenias (ITs) are heterogeneous genetic disorders that frequently represent a diagnostic challenge. The requirement of highly specialized tests for diagnosis represents a particular problem in resource-limited settings. To overcome this difficulty, we applied a diagnostic algorithm and developed a collaboration program with a specialized international center in order to increase the diagnostic yield in a cohort of patients in Argentina. METHODS: Based on the algorithm, initial evaluation included collection of clinical data, platelet size, blood smear examination and platelet aggregation tests. Confirmatory tests were performed according to diagnostic suspicion, which included platelet glycoprotein expression, immunofluorescence for myosin-9 in granulocytes and platelet thrombospondin-1 and molecular screening of candidate genes. RESULTS: Thirty-one patients from 14 pedigrees were included; their median age was 32 (4-72) years and platelet count 72 (4-147)×10(9) L(-1). Autosomal dominant inheritance was found in nine (64%) pedigrees; 10 (71%) had large platelets and nine (29%) patients presented with syndromic forms. A definitive diagnosis was made in 10 of 14 pedigrees and comprised MYH9-related disease in four, while classic and monoallelic Bernard-Soulier syndrome, gray platelet syndrome, X-linked thrombocytopenia, thrombocytopenia 2 (ANKRD26 mutation) and familial platelet disorder with predisposition to acute myelogenous leukemia were diagnosed in one pedigree each. CONCLUSIONS: Adoption of an established diagnostic algorithm and collaboration with an expert referral center proved useful for diagnosis of IT patients in the setting of a developing country. This initiative may serve as a model to develop international networks with the goal of improving diagnosis and care of patients with these rare diseases.
Keywords: Adolescent; Adult; Aged; Algorithms; Argentina; Biological Markers; Child; Child, Preschool; Cooperative Behavior; Developing Countries; DNA Mutational Analysis; Feasibility Studies; Female; Flow Cytometry; Fluorescent Antibody Technique; Genetic Predisposition to Disease; Genetic Testing; Health Services Accessibility; Hematologic Tests; Heredity; Humans; International Cooperation; Italy; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Pedigree; Phenotype; Platelet Count; Platelet Function Tests; Predictive Value of Tests; Prognosis; Referral and Consultation; Thrombocytopenia; Thrombospondin 1; Young Adult

Involuntary movements after correction of vitamin B12 deficiency: a video-case report. - Zanus, Caterina; Alberini, Elena; Costa, Paola; Colonna, Franco; Zennaro, Floriana; Carrozzi, Marco (Epileptic Disord, 2012)
Involuntary movements can appear before and after initiation of vitamin B12 treatment. The pathogenesis of involuntary movements in vitamin B12 deficiency and their relationship with cobalamin injection remain unclear due to a lack of video-EEG documentation making the electroclinical correlation difficult to ascertain. Here, we report video-EEG and neuroimaging findings of an 11-month-old girl with vitamin B12 deficiency, who acutely developed involuntary movements a few days after initiation of vitamin B12 treatment with normal vitamin plasmatic levels. Abnormal movements were a combination of tremor and myoclonus involving the face, mouth, and left arm, which disappeared after discontinuation of therapy. [Published with video sequences].
Keywords: Atrophy; Brain; Dyskinesias; Electroencephalography; Female; Humans; Infant; Magnetic Resonance Imaging; Myelin Sheath; Myoclonus; Tremor; Video Recording; Vitamin B 12; Vitamin B 12 Deficiency; Vitamins

In vivo distribution of β2 glycoprotein I under various pathophysiologic conditions. - Agostinis, Chiara; Biffi, Stefania; Garrovo, Chiara; Durigutto, Paolo; Lorenzon, Andrea; Bek, Alpan; Bulla, Roberta; Grossi, Claudia; Borghi, Maria O; Meroni, Pierluigi; Tedesco, Francesco (Blood, 2011)
In vitro studies have documented β2 glycoprotein I (β2GPI) binding to endothelial cells (ECs) and trophoblast using antiphospholipid antibodies. The in vivo binding of β2GPI to these cells and the conditions that favor their interaction have not been investigated. We analyzed the in vivo distribution of cyanine 5.5-labeled β2GPI in mice and evaluated the effect of pregnancy and circulating antibodies on its tissue localization. The signal was detected in the liver by whole body scan and ex vivo analysis. The β2GPI failed to bind to the vascular endothelium and reacted only with the ECs of uterine vessels. In pregnant mice the protein was localized on ECs and trophoblast at the embryo implantation sites. Immunized mice showed a similar β2GPI biodistribution to naive mice but the immunized pregnant animals exhibited a significant increase in fetal loss associated with C3 and C9 deposition at the implantation sites. Treatment of mice with LPS after β2GPI-Cy5.5 injection promoted protein localization on gut and brain ECs associated with IgG, C1q, and C9 deposition in immunized mice. These findings indicate that β2GPI binding to EC requires priming with pro-inflammatory factors which is not needed for uterine and placental localization probably dependent on hormonal changes.
Keywords: Animals; beta 2-Glycoprotein I; Complement C1q; Complement C3; Complement C9; Endothelial Cells; Endothelium, Vascular; Female; Fetal Death; Humans; Mice; Mice, Inbred BALB C; Pregnancy; Trophoblasts; Uterus

Interventions for the prevention of overweight and obesity in preschool children: a systematic review of randomized controlled trials. - Monasta, L; Batty, G D; Macaluso, A; Ronfani, L; Lutje, V; Bavcar, A; van Lenthe, F J; Brug, J; Cattaneo, A (Obes Rev, 2011)
The objective of this study was to analyse interventions for the prevention of overweight and obesity in children under 5 years of age. We carried out a systematic review focusing exclusively on randomized controlled trials (RCTs). Data sources include Medline, Cochrane Library, EMBASE, CINHAL, PsychInfo and Web of Science. Data were extracted from seventeen articles describing seven RCTs identified through electronic search, screening of references in systematic reviews, own files and contact with authors. RCTs were assessed with the Jadad scale. Four trials were carried out in preschool settings, one with an exclusive educational component, two with an exclusive physical activity component and one with both. Two trials were family-based, with education and counselling for parents and children. The remaining trial was carried out in maternity hospitals, with a training intervention on breastfeeding. None of the interventions had an effect in preventing overweight and obesity. The failure to show an effect may be due to the choice of outcomes, the quality of the RCTs, the suboptimal implementation of the interventions, the lack of focus on social and environmental determinants. More rigorous research is needed on interventions and on social and environmental factors that could impact on lifestyle.
Keywords: Child Nutrition Sciences; Child Nutritional Physiological Phenomena; Child, Preschool; Exercise; Female; Health Promotion; Humans; Life Style; Male; Obesity; Overweight; Randomized Controlled Trials as Topic

Intranasal lidocaine and midazolam for procedural sedation in children. - Chiaretti, Antonio; Barone, Giuseppe; Rigante, Donato; Ruggiero, Antonio; Pierri, Filomena; Barbi, Egidio; Barone, Giovanni; Riccardi, Riccardo (Arch Dis Child, 2011)
OBJECTIVE: To evaluate the safety and efficacy of a sedation protocol based on intranasal lidocaine spray and midazolam (INM) in children who are anxious and uncooperative when undergoing minor painful or diagnostic procedures, such as peripheral line insertion, venipuncture, intramuscular injection, echocardiogram, CT scan, audiometry testing and dental examination and extractions. PATIENTS AND DESIGN: 46 children, aged 5-50 months, received INM (0.5 mg/kg) via a mucosal atomiser device. To avoid any nasal discomfort a puff of lidocaine spray (10 mg/puff) was administered before INM. The child's degree of sedation was scored using a modified Ramsay sedation scale. A questionnaire was designed to evaluate the parents' and doctors' opinions on the efficacy of the sedation. Statistical analysis was used to compare sedation times with children's age and weight. RESULTS: The degree of sedation achieved by INM enabled all procedures to be completed without additional drugs. Premedication with lidocaine spray prevented any nasal discomfort related to the INM. The mean duration of sedation was 23.1 min. The depth of sedation was 1 on the modified Ramsay scale. The questionnaire revealed high levels of satisfaction by both doctors and parents. Sedation start and end times were significantly correlated with age only. No side effects were recorded in the cohort of children studied. CONCLUSIONS: This study has shown that the combined use of lidocaine spray and atomised INM appears to be a safe and effective method to achieve short-term sedation in children to facilitate medical care and procedures.
Keywords: Administration, Intranasal; Anesthetics, Local; Anxiety; Child, Preschool; Conscious Sedation; Diagnostic Techniques and Procedures; Female; Humans; Hypnotics and Sedatives; Infant; Lidocaine; Male; Midazolam; Minimally Invasive Surgical Procedures; Nebulizers and Vaporizers; Nose Diseases; Prospective Studies

Incidence of bacteremias and invasive mycoses in children with acute non-lymphoblastic leukemia: results from a multi-center Italian study. - Castagnola, Elio; Rossi, Mario R; Cesaro, Simone; Livadiotti, Susanna; Giacchino, Mareva; Zanazzo, Giulio; Fioredda, Francesca; Beretta, Chiara; Ciocchello, Francesca; Carli, Modesto; Putti, Maria Caterina; Pansini, Valeria; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: Data on the epidemiology of bacteremias and invasive fungal diseases (IFD) in children with acute myeloid leukemia (AML) are scarce. DESIGN AND METHODS: In a multi-center, retrospective study, we analyzed proportion, rate per 1,000 person-days at risk, and cumulative risk of bacteremias and IFD in children with AML. RESULTS: Between January 1998 and December 2005, 240 children were treated for AML at 8 Italian Centers, for a total of 521 treatment courses and 63,232 person-days at risk. Bacteremia was observed in 32% of treatment courses and IFD was seen in 10% (P < 0.0001), with rates of 2.62 and 0.84, respectively (P < 0.001). There was a significantly higher frequency of IFD during relapse treatment: proportion 15% versus 9% (P = 0.05), rate 2.10 versus 0.64 (P = 0.008) and cumulative risk 32% versus 12% (P = 0.007), while there were no differences in the proportion, rate and cumulative risk of bacteremia during front-line or relapse treatment. The epidemiology of bacteremias and IFD was different during front-line therapy for M3 as compared to other types of AML, but the differences were not statistically significant. CONCLUSIONS: Severe infectious complications are frequent during the treatment of pediatric AML, especially during relapse treatment, and bacteremias are more frequent than IFD.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Bacteremia; Child; Female; Follow-Up Studies; Humans; Incidence; Italy; Leukemia, Myeloid, Acute; Male; Mycoses; Neoplasm Recurrence, Local; Retrospective Studies

Individual differences in prefrontal cortex activity during perception of bitter taste using fNIRS methodology. - Bembich, Stefano; Lanzara, Carmela; Clarici, Andrea; Demarini, Sergio; Tepper, Beverly J; Gasparini, Paolo; Grasso, Domenico L (Chem Senses, 2010)
Although bitter taste has a crucial role in nutrition by preventing the ingestion of toxic foods, there are few studies on bitter taste neuroimaging. To identify cortical areas involved in bitter taste perception and to determine if individual differences in taste sensitivity to 6-n-propylthiouracil (PROP) are represented in the brain by different cortical activation patterns, we examined 48 healthy volunteers using functional near-infrared spectroscopy. Participants rated the perceived intensity of filter paper disks impregnated with PROP and NaCl during the imaging procedure and were then classified as PROP tasters and nontasters. We monitored cortical activity in both the anterior and posterior regions of the dorsolateral prefrontal cortex (DLPFC) and in the ventrolateral prefrontal cortex (VLPFC). No activity was detected in the anterior DLPFC in any of the participants. However, during the administration of PROP, significant cortical activation was detected in the more posterior regions of the left DLPFC and in the left and right VLPFC but only in PROP tasters. PROP nontasters showed no cortical activity in these areas. These data suggest that the prefrontal cortex is involved in the conscious perception of the bitter taste of PROP and that the pattern of activity is consistent with individual differences in the ability to taste this compound. Thus, the PROP phenotype is associated with fundamental differences in cortical taste processing.
Keywords: Adult; Eating; Female; Food Preferences; Humans; Individuality; Male; Perception; Phenotype; Prefrontal Cortex; Propylthiouracil; Sodium Chloride; Spectroscopy, Near-Infrared; Taste; Taste Threshold; Young Adult

Insights into the binding of Phenyltiocarbamide (PTC) agonist to its target human TAS2R38 bitter receptor. - Biarnés, Xevi; Marchiori, Alessandro; Giorgetti, Alejandro; Lanzara, Carmela; Gasparini, Paolo; Carloni, Paolo; Born, Stephan; Brockhoff, Anne; Behrens, Maik; Meyerhof, Wolfgang (PLoS One, 2010)
Humans' bitter taste perception is mediated by the hTAS2R subfamily of the G protein-coupled membrane receptors (GPCRs). Structural information on these receptors is currently limited. Here we identify residues involved in the binding of phenylthiocarbamide (PTC) and in receptor activation in one of the most widely studied hTAS2Rs (hTAS2R38) by means of structural bioinformatics and molecular docking. The predictions are validated by site-directed mutagenesis experiments that involve specific residues located in the putative binding site and trans-membrane (TM) helices 6 and 7 putatively involved in receptor activation. Based on our measurements, we suggest that (i) residue N103 participates actively in PTC binding, in line with previous computational studies. (ii) W99, M100 and S259 contribute to define the size and shape of the binding cavity. (iii) W99 and M100, along with F255 and V296, play a key role for receptor activation, providing insights on bitter taste receptor activation not emerging from the previously reported computational models.
Keywords: Amino Acid Sequence; Calcium; Cell Line; Computational Biology; Dose-Response Relationship, Drug; Humans; Intracellular Space; Ligands; Models, Molecular; Molecular Sequence Data; Mutagenesis, Site-Directed; Phenylthiourea; Protein Binding; Protein Structure, Secondary; Receptors, G-Protein-Coupled